Adhesive Sheet for Wafer Processing

By using adhesive sheets in wafer processing, the combination of aqueous stripping liquid and active energy rays can reduce the sticky and slippage phenomenon, and the problem of damage to thin wafers during processing is solved, achieving a lighter peeling force and higher Productivity.

CN112980345BActive Publication Date: 2025-02-18NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202011463463.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-13
Filing Date
2020-12-11
Publication Date
2025-02-18
Estimated Expiration
2040-12-11

AI Technical Summary

Technical Problem

When processing thin wafers, it is easy to cause damage to the wafer, especially during the back grinding process, the sticky and slip of the adhesive sheet leads to an increase in the load during peeling, which in turn damages the wafer.

Method used

It is provided with a wafer processing adhesive sheet including an adhesive layer forming an adhesive surface, which uses an aqueous stripping liquid, an active energy ray or a combination of both under a peeling speed of 300 mm/min. Methods: The measured viscosity and slippage is less than 30 to reduce the viscosity and slippage during peeling.

Benefits of technology

By suppressing sticky and slippage during peeling, the load on the wafer is reduced, the risk of wafer damage is reduced, and the production efficiency and product quality are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112980345B_ABST
    Figure CN112980345B_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide an adhesive sheet for wafer processing that can suppress the stick-slip phenomenon during peeling. According to the present application, an adhesive sheet for wafer processing comprising an adhesive layer constituting an adhesive surface can be provided. For the above-mentioned adhesive sheet, an evaluation sample is prepared by attaching the above-mentioned adhesive surface of the adhesive sheet to a silicon wafer as an adherend, and the stick-slip property [10 ‑3 N / 10mm] is less than 30.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet for wafer processing. Background Art

[0002] In the manufacturing process of semiconductor devices, the process of grinding, cutting and other processing is usually carried out on a wafer (typically a semiconductor wafer) having a circuit forming surface, with an adhesive sheet attached to the side of the circuit forming surface. As an adhesive sheet, an adhesive sheet in the form of an adhesive layer is usually used on at least one side of the substrate. For example, when the back of a semiconductor wafer is ground (back grinding), in order to protect the circuit forming surface (front) of the semiconductor wafer and to hold the semiconductor wafer, a back grinding tape (for example, patent document 1) is used.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-212441

[0006] Patent Document 2: Japanese Patent Application Publication No. 2014-003199 Summary of the invention

[0007] Problems to be solved by the invention

[0008] In recent years, along with the miniaturization, thinning and high integration of semiconductor devices, the demand for thinning of wafers has increased. However, when processing thin wafers, it will be more likely to cause damage to the wafers. For example, if the back surface is ground until the wafer becomes thinner, the load when peeling off the back surface grinding tape is likely to cause the wafer to be damaged, and a decrease in the yield rate and a decrease in productivity due to the cautious peeling operation may occur. In particular, as described in Patent Document 2, for a wafer whose back surface is ground in a manner such that the inner side of the annular protrusion becomes a recessed portion (the so-called TAIKO (registered trademark) wafer), if the above-mentioned annular protrusion is adsorbed and the wafer is fixed, the back surface becomes unsupported in the above-mentioned recessed portion, and therefore, damage is particularly likely to occur when the back surface grinding tape is peeled off.

[0009] One of the important reasons for the damage to the wafer when the adhesive sheet is peeled off from the wafer as the adherend is the stick-slip phenomenon of the adhesive sheet. The so-called stick-slip phenomenon refers to the phenomenon that when the adhesive sheet is peeled off from the adherend, the peeling is intermittent due to the combination of multiple peeling modes such as interfacial peeling from the adherend surface (peeling surface) and cohesive failure inside the adhesive. When the stick-slip phenomenon occurs, the peeling force vibrates greatly as the peeling proceeds. Therefore, the burden imposed on the adherend during peeling becomes further increased, which will become an important cause of damage to the adherend.

[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a pressure-sensitive adhesive sheet for wafer processing that can reduce the load applied to an adherend by suppressing the stick-slip phenomenon during peeling.

[0011] Means for solving problems

[0012] According to the present specification, there is provided an adhesive sheet for wafer processing comprising an adhesive layer constituting an adhesive surface. Here, for the adhesive sheet, an evaluation sample is used in which the adhesive surface of the adhesive sheet is attached to a silicon wafer as an adherend, and the tackiness [10 -3 N / 10mm] is less than 30.

[0013] (Method A) An aqueous peeling liquid is supplied to the interface between the PSA sheet and the adherend in the evaluation sample, and then the stickiness when the PSA sheet is peeled from the adherend is measured.

[0014] (Method B) The evaluation sample was irradiated with active energy rays from the surface of the PSA sheet opposite to the adherend, and then the stickiness when the PSA sheet was peeled from the adherend was measured.

[0015] (Method C) The evaluation sample is irradiated with active energy rays from the surface of the PSA sheet opposite to the adherend, and an aqueous peeling liquid is supplied to the interface between the PSA sheet and the adherend, and then the stickiness when the PSA sheet is peeled from the adherend is measured.

[0016] The above-mentioned adhesive sheet for wafer processing can suppress the stick-slip phenomenon during peeling, so that the load applied to the adherend during peeling can be reduced, and damage to the adherend can be suppressed.

[0017] In some preferred aspects of the technology disclosed in this specification, the peel strength of the pressure-sensitive adhesive sheet measured by at least one of the following methods E, F, and G using the evaluation sample is 0.10 N / 10 mm or less.

[0018] (Method E) An aqueous peeling liquid is supplied to the interface between the PSA sheet and the adherend in the evaluation sample, and then the peeling force when the PSA sheet is peeled from the adherend is measured.

[0019] (Method F) The evaluation sample was irradiated with active energy rays from the surface of the pressure-sensitive adhesive sheet opposite to the adherend, and then the peeling force when the pressure-sensitive adhesive sheet was peeled from the adherend was measured.

[0020] (Method G) The evaluation sample is irradiated with active energy rays from the surface of the PSA sheet opposite to the adherend, and an aqueous peeling liquid is supplied to the interface between the PSA sheet and the adherend, and then the peeling force when the PSA sheet is peeled from the adherend is measured.

[0021] The pressure-sensitive adhesive sheet for wafer processing can be peeled off with a light peeling force in the peeling step of peeling off from the adherend, so that the burden on the adherend during the peeling can be reduced.

[0022] In a preferred embodiment of the technology disclosed in this specification, for the above-mentioned adhesive sheet, the above-mentioned evaluation sample is used, and the peeling force when the above-mentioned adhesive sheet is peeled off from the above-mentioned adherend in a manner not irradiating the evaluation sample with active energy rays is 0.20N / 10mm or more. For the above-mentioned wafer processing adhesive sheet, it is easy to show high adhesion when it is not irradiated with active energy rays. Therefore, in the process (such as the back grinding process) of processing the adherend in the state where the above-mentioned adhesive sheet is attached to the adherend, it is easy to suppress the adhesive sheet from being peeled off from the adherend.

[0023] In a preferred embodiment of the technology disclosed in this specification, the adhesive layer is an active energy ray-curable adhesive layer. Through the adhesive sheet, after irradiation with active energy rays, the peeling force is easily reduced, and therefore, before and after irradiation with active energy rays, the peeling force changes greatly. Therefore, for the above-mentioned adhesive sheet, it is easy to achieve the adhesive force in the processing step (such as the back grinding step) and the light peeling in the peeling step at the same time. In addition, through the above-mentioned adhesive sheet, the stickiness after irradiation with active energy rays is easily reduced, therefore, it is easy to become an adhesive sheet that suppresses the burden given to the adherend during peeling, and it is easy to suppress the damage of the adherend during peeling.

[0024] In a preferred embodiment of the technology disclosed in this specification, for the above-mentioned adhesive sheet, the stickiness [10 - 3N / 10mm] is 10 or less. The above-mentioned pressure-sensitive adhesive sheet for wafer processing can further suppress the stick-slip phenomenon during peeling, thereby further reducing the load applied to the adherend and further suppressing damage to the adherend.

[0025] In a preferred embodiment of the technology disclosed in this specification, for the above-mentioned pressure-sensitive adhesive sheet, the stickiness [10 -3 N / 10mm] is less than 3. The above-mentioned pressure-sensitive adhesive sheet for wafer processing can particularly suppress the stick-slip phenomenon during peeling, thereby further reducing the load applied to the adherend and further suppressing damage to the adherend.

[0026] In a preferred embodiment of the technology disclosed in this specification, the peeling force of the adhesive sheet is less than 0.050 N / 10 mm when measured by at least one of the method F and the method G using the evaluation sample. The adhesive sheet for wafer processing can achieve particularly remarkable light peeling in the peeling step of peeling from the adherend.

[0027] It should be noted that the scope of the invention claimed to be protected by this patent application may also include solutions formed by appropriate combinations of the above-mentioned elements. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] [ Figure 1 ] is a cross-sectional view schematically showing a structural example of an adhesive sheet for chip processing.

[0029] [ Figure 2 ] is a cross-sectional view schematically showing another structural example of an adhesive sheet for chip processing.

[0030] [ Figure 3 ] is a cross-sectional view schematically showing another structural example of an adhesive sheet for chip processing.

[0031] [ Figure 4 ] is a cross-sectional view schematically showing another structural example of an adhesive sheet for chip processing.

[0032] [ Figure 5 ] is a cross-sectional view schematically showing another structural example of an adhesive sheet for chip processing.

[0033] [ Figure 6 ] is a cross-sectional view schematically showing another structural example of an adhesive sheet for chip processing.

[0034] [ Figure 7 ] is a diagram schematically showing the peeling force of a wafer processing pressure-sensitive adhesive sheet from an adherend (x-axis: peeling distance, y-axis: peeling force).

[0035] Description of Reference Numerals

[0036] 1, 2, 3, 4, 5, 6 Adhesive sheets for wafer processing

[0037] 10. Substrate

[0038] 10A Side 1

[0039] 10B Side 2

[0040] 21, 22 Adhesive layer

[0041] 21A First bonding surface

[0042] 21B Second adhesive surface

[0043] 31, 32 Release liner

[0044] x Peel distance

[0045] y Peel force

[0046] SS sticky

[0047] L Base length DETAILED DESCRIPTION

[0048] The preferred embodiments of the present invention are described below. It should be noted that, with respect to matters necessary for the implementation of the present invention other than those specifically described in this specification, those skilled in the art can understand based on the teachings of implementing the invention described in this specification and the technical common sense at the time of application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in this field. In addition, in the following drawings, components and parts that play the same role are sometimes marked with the same figure marks for description, and sometimes repeated descriptions are omitted or simplified. In addition, for the embodiments described in the drawings, they are schematically shown in order to clearly illustrate the present invention, and the size and proportion of the product actually provided may not be correctly represented.

[0049] In this specification, the main chain of a polymer refers to the chain structure forming the backbone of the polymer. In addition, the side chain of a polymer refers to a group (pendant) bonded to the main chain or a molecular chain that can be regarded as a pendant.

[0050] In this specification, the term "acrylic polymer" refers to a polymer derived from a monomer raw material containing more than 50% by weight (preferably more than 70% by weight, for example more than 90% by weight) of an acrylic monomer. The above-mentioned acrylic monomer refers to a monomer having at least one (meth)acryloyl group in one molecule. In addition, in this specification, the term "(meth)acryloyl" means a meaning including both acryloyl and methacryloyl. Similarly, the term "(meth)acrylate" means a meaning including both acrylate and methacrylate, and the term "(meth)acrylic-" means a meaning including both acrylic- and methacrylic-, respectively.

[0051] In the present specification, the term “active energy rays” refers to a concept including light such as ultraviolet rays, visible rays, and infrared rays, and radiation such as α rays, β rays, γ rays, electron beams, neutron beams, and X-rays.

[0052] <Characteristics of adhesive sheets>

[0053] The adhesive sheet for wafer processing disclosed in this specification is an adhesive sheet for wafer processing that ideally suppresses the stick-slip phenomenon generated when peeling from an adherend. Here, in this specification, the degree of the stick-slip phenomenon generated when the adhesive sheet is peeled from the adherend is referred to as "stick-slip degree". For the adhesive sheet disclosed in this specification, in a preferred embodiment, the stick-slip degree is suppressed to a lower value below a specified value. Such an adhesive sheet can ideally suppress the stick-slip phenomenon generated when peeling from an adherend, and therefore can suppress the large vibration of the peeling force that occurs with the peeling, and can reduce the burden imposed on the adherend. Therefore, by using an adhesive sheet with low stick-slip degree, it is easy to suppress damage to the adherend during peeling.

[0054] Regarding the method for measuring "stickiness" in this specification, refer to Figure 7 Provide explanation. Figure 7 It is a graph of a general peel force curve of an adhesive sheet (the x-axis is the peel distance, and the y-axis is the peel force). For the stickiness SS of the adhesive sheet, the peel force curve is represented by y=f(x), and when only the reference length L is extracted from the peel force curve along the direction of its average line, it is calculated by the following general formula (1). Here, in the initial peeling period from the time when the adhesive sheet is peeled off from the adherend to the formation of the specified peeling behavior, the peeling behavior of the adhesive sheet is often not in a stable state. Therefore, the measurement of the stickiness is preferably started from the position where the adhesive sheet is peeled off from the adherend to a specified distance. In addition, the reference length L can be appropriately set according to the peeling behavior of the adhesive sheet, etc. The stickiness of the adhesive sheet described here [10 -3 N / 10 mm] can be specifically measured by the method described in the examples described later.

[0055] [Mathematical formula 1]

[0056]

[0057] For the adhesive sheet disclosed in this specification, the stickiness [10 -3 N / 10mm] is suppressed to be below the specified value. By such an adhesive sheet, the stick-slip phenomenon can be suppressed, so it is easy to suppress the damage of the adherend during peeling.

[0058] In a preferred embodiment of the adhesive sheet disclosed in this specification, the stickiness [10 -3 N / 10mm] is suppressed to a lower value than the specified value. With such an adhesive sheet, the stick-slip phenomenon during peeling can be further suppressed, so there is a tendency to further suppress damage to the adherend during peeling. From the same point of view, the stick-slip [10 -3 A PSA sheet in which the [N / 10 mm] is suppressed to a lower value than a prescribed value is preferred.

[0059] Method A: An aqueous peeling liquid is supplied to the interface between the PSA sheet and the adherend in the evaluation sample, and then the stickiness SSw0 when the PSA sheet is peeled from the adherend is measured.

[0060] Method B: The evaluation sample is irradiated with active energy rays from the surface of the PSA sheet opposite to the adherend, and then the stickiness SSd1 when the PSA sheet is peeled from the adherend is measured.

[0061] Method C: The evaluation sample is irradiated with active energy rays from the surface of the PSA sheet opposite to the adherend, and an aqueous peeling liquid is supplied to the interface between the PSA sheet and the adherend, and then the stickiness SSw1 when the PSA sheet is peeled from the adherend is measured.

[0062] In a preferred embodiment of the adhesive sheet disclosed in this specification, the viscosity SSw0 measured by the above-mentioned method A (hereinafter also referred to as "non-irradiated water peeling viscosity SSw0") can be about 150 or less. From the viewpoint of suppressing damage to the adherend during peeling, in some embodiments, the non-irradiated water peeling viscosity SSw0 can be, for example, 100 or less, 50 or less, preferably 30 or less, more preferably 25 or less, and 22 or less. There is no particular restriction on the lower limit of the non-irradiated water peeling viscosity SSw0. From the viewpoint of achieving a balance with the adhesive properties, it can be, for example, 0.5 or more, 1 or more, 5 or more, 10 or more, and 15 or more. It should be noted that for the above-mentioned non-irradiated water peeling viscosity SSw0, when the adhesive layer of the adhesive sheet is an active energy ray-curable adhesive layer, the value measured when the adhesive sheet is peeled off from the adherend by water in the evaluation sample in which the active energy ray is not irradiated to the above-mentioned adhesive sheet is adopted.

[0063] In a preferred embodiment of the adhesive sheet disclosed in this specification, the viscosity SSd1 measured by the above-mentioned method B (hereinafter also referred to as "normal peeling viscosity SSd1 after irradiation") can be about 100 or less. From the viewpoint of suppressing damage to the adherend during peeling, in some embodiments, the normal peeling viscosity SSd1 after irradiation can be, for example, 50 or less, preferably 30 or less, more preferably 20 or less, and further preferably 15 or less (for example, 10 or less). There is no particular limitation on the lower limit of the normal peeling viscosity SSd1 after irradiation. From the viewpoint of achieving a balance with the adhesive properties, it can be, for example, 0.10 or more, 0.50 or more, 1.0 or more, 1.50 or more, or 2.0 or more.

[0064] In a preferred embodiment of the adhesive sheet disclosed in this specification, the viscosity SSw1 measured by the above-mentioned method C (hereinafter also referred to as "post-irradiation water peeling viscosity SSw1") can be about 100 or less. From the viewpoint of suppressing damage to the adherend during peeling, in some embodiments, the post-irradiation water peeling viscosity SSw1 can be, for example, 50 or less, preferably 30 or less, more preferably 20 or less, further preferably 10 or less (for example, less than 3), and can be less than 1. There is no particular limitation on the lower limit of the post-irradiation water peeling viscosity SSw1, and from the viewpoint of achieving a balance with the adhesive properties, it can be, for example, 0.01 or more, 0.10 or more, 0.20 or more, or 0.25 or more.

[0065] It should be noted that there is no particular limitation on the stickiness SSd0 (hereinafter also referred to as "non-irradiated conventional peeling stickiness SSd0") when the adhesive sheet is conventionally peeled off from the adherend without irradiating the adhesive sheet with active energy rays (i.e., peeled off without using a peeling liquid such as an aqueous peeling liquid) using the evaluation sample. From the viewpoint of achieving a balance with the adhesive properties, the non-irradiated conventional peeling stickiness SSd0 is usually preferably 1.0 to 200, may be 5.0 to 150, may be 10 to 100, may be 15 to 50, may be 15 to 30, or may be 15 to 25.

[0066] In a preferred embodiment of the technology disclosed in this specification, for the above-mentioned adhesive sheet, the peeling force measured by at least one of the following methods E, F and G using the above-mentioned evaluation sample is suppressed to a lower value than a specified value. With such an adhesive sheet, light peeling can be achieved in the peeling process, so it is easy to suppress damage to the adherend during peeling. The peeling force of the adhesive sheet can be specifically measured by the method described in the examples described later.

[0067] In a preferred embodiment of the adhesive sheet disclosed in this specification, the peeling force measured by at least one of the following methods F and G is suppressed to a lower value than a specified value. With such an adhesive sheet, lighter peeling can be achieved in the peeling process, so it is easy to suppress damage to the adherend during peeling. From the same point of view, an adhesive sheet whose peeling force measured by the following method G is suppressed to a lower value than a specified value is more preferred.

[0068] In a preferred embodiment of the technology disclosed in this specification, the peeling force of the pressure-sensitive adhesive sheet measured by the following method H using the evaluation sample is greater than or equal to a predetermined value. Such a pressure-sensitive adhesive sheet can easily exhibit a desired adhesive force in a processing step such as back grinding.

[0069] Method E: An aqueous peeling liquid is supplied to the interface between the PSA sheet and the adherend in the evaluation sample, and then a peeling force Fw0 when the PSA sheet is peeled from the adherend is measured.

[0070] Method F: The evaluation sample is irradiated with active energy rays from the surface of the PSA sheet opposite to the adherend, and then the peeling force Fd1 when the PSA sheet is peeled from the adherend is measured.

[0071] Method G: The evaluation sample is irradiated with active energy rays from the surface of the PSA sheet opposite to the adherend, and an aqueous peeling liquid is supplied to the interface between the PSA sheet and the adherend, and then the peeling force Fw1 when the PSA sheet is peeled from the adherend is measured.

[0072] Method H: The peeling force Fd0 when the pressure-sensitive adhesive sheet is peeled off from the adherend is measured without irradiating the evaluation sample with active energy rays.

[0073] In a preferred embodiment of the technology disclosed in this specification, the peeling force Fw0 measured by the above-mentioned method E (hereinafter also referred to as "non-irradiated water peeling force Fw0") is usually preferably 5.0N / 10mm or less, preferably 2.0N / 10mm or less, more preferably 1.0N / 10mm or less, and further preferably 0.50N / 10mm or less (for example, 0.10N / 10mm or less). There is no particular restriction on the lower limit of the non-irradiated water peeling force Fw0. From the perspective of improving the adhesion to the adherend, in some embodiments, it is preferably 0.01N / 10mm or more, for example, 0.02N / 10mm or more, 0.03N / 10mm or more, 0.05N / 10mm or more, 0.075N / 10mm or more, or 0.08N / 10mm or more. Note that, for the unirradiated water peeling force Fw0, when the PSA layer of the PSA sheet is an active energy ray-curable PSA layer, the value measured when the PSA sheet is water-peeled from an adherend in an evaluation sample before irradiating the PSA sheet with active energy rays is used.

[0074] In a preferred embodiment of the technology disclosed in this specification, the peel force Fd1 measured by the above-mentioned method F (hereinafter also referred to as "normal peel force Fd1 after irradiation") is usually preferably 1.0 N / 10 mm or less, preferably 0.10 N / 10 mm or less, more preferably 0.08 N / 10 mm or less, and further preferably 0.05 N / 10 mm or less (for example, 0.03 N / 10 mm or less). There is no particular restriction on the lower limit of the normal peel force Fd1 after irradiation. From the perspective of achieving a balance with the adhesive performance, in some embodiments, it can be 0.001 N / 10 mm or more, 0.002 N / 10 mm or more, or 0.004 N / 10 mm or more.

[0075] In a preferred embodiment of the technology disclosed in this specification, the peeling force Fw1 measured by the above-mentioned method G (hereinafter also referred to as "water peeling force Fw1 after irradiation") is usually preferably 1.0 N / 10 mm or less, preferably 0.10 N / 10 mm or less, more preferably 0.05 N / 10 mm or less, and further preferably 0.01 N / 10 mm or less (for example, 0.008 N / 10 mm or less). There is no particular restriction on the lower limit of the water peeling force Fw1 after irradiation. From the perspective of achieving a balance with the adhesive performance, in some embodiments, it can be 0.0005 N / 10 mm or more, 0.001 N / 10 mm or more, or 0.002 N / 10 mm or more.

[0076] In a preferred embodiment of the technology disclosed in this specification, the peeling force Fd0 measured by the above-mentioned method H (hereinafter also referred to as "non-irradiated conventional peeling force Fd0") is usually preferably 0.05N / 10mm or more, preferably 0.10N / 10mm or more, more preferably 0.20N / 10mm or more, and further preferably 0.30N / 10mm or more. From the perspective of improving the adhesion to the adherend during wafer (typically, semiconductor wafer) processing, in some embodiments, the non-irradiated conventional peeling force Fd0 is preferably 0.50N / 10mm or more, more preferably 1.0N / 10mm or more, and further preferably 1.50N / 10mm or more (for example, 2.0N / 10mm or more). There is no particular upper limit on the unirradiated conventional peeling force Fd0. From the perspective of achieving light peeling during peeling, it is usually suitable to be about 15 N / 10 mm or less, preferably 10 N / 10 mm or less, more preferably 5.0 N / 10 mm or less, and can be 3.0 N / 10 mm or less, and can be 1.0 N / 10 mm or less.

[0077] As a tensile testing machine used in the measurement of the conventional peeling viscosity SSd0, SSd1 and the water peeling viscosity SSw0, SSw1, a precision universal testing machine "Model: VPA-3" manufactured by Kyowa Interface Science Co., Ltd. or an equivalent device can be used. During the measurement, if necessary, a suitable lining material (for example, a PET film with a thickness of about 25 μm) can be attached to the pressure-sensitive adhesive sheet to be measured for reinforcement.

[0078] As the tensile testing machine used in the measurement of the conventional peeling forces Fd0, Fd1 and the water peeling forces Fw0, Fw1, a precision universal testing machine "Model: DT9503-1000N" manufactured by Tansui Co., Ltd. or an equivalent device can be used. During the measurement, if necessary, a suitable lining material (for example, a PET film with a thickness of about 25 μm) can be attached to the adhesive sheet to be measured for reinforcement.

[0079] As the silicon wafer as an adherend used in preparing the above-mentioned evaluation sample, the same or equivalent products as those in the examples described below can be used. It should be noted that the adhesive sheet disclosed in this specification is not limited to being used for the same wafer as the silicon wafer used in preparing the above-mentioned evaluation sample. That is, the use of the adhesive sheet disclosed in this specification is not limited to the processing of the silicon wafer as an adherend used in the measurement of stickiness and / or peeling force, but can also be used for other wafer processing.

[0080] <Structural example of adhesive sheet>

[0081] The wafer processing adhesive sheet disclosed in this specification is equipped with an adhesive layer. Typically, the adhesive layer constitutes at least one surface of the adhesive sheet. The adhesive sheet can be an adhesive sheet with a substrate in the form of an adhesive layer on one or both sides of a substrate (support), or an adhesive sheet (adhesive sheet without substrate) in the form of a substrate.

[0082] The concept of the so-called adhesive sheet here may include products called adhesive tapes, adhesive labels, adhesive films, etc. In addition, typically, the above-mentioned adhesive layer can be formed continuously, but is not limited to the above-mentioned form, for example, it can be an adhesive layer formed into regular or irregular patterns such as dot-shaped and striped. In addition, the adhesive sheet provided by this specification can be in a roll or a monolithic form. Alternatively, it can also be an adhesive sheet further processed into a form of various shapes.

[0083] The adhesive sheet disclosed in this specification may be, for example, Figure 1 to Figure 6 The cross-sectional structure of the adhesive sheet is schematically shown in FIG. Figure 1 , Figure 2 This is an example of a structure of a PSA sheet with a substrate that is adhesive on one side (single-sided PSA sheet with a substrate). Figure 1 The PSA sheet 1 shown has a structure in which a PSA layer 21 is provided on one side 10A (non-releasable) of a substrate 10 , and a surface (adhesive surface) 21A of the PSA layer 21 is protected by a release liner 31 at least on which the PSA layer side serves as a release surface. Figure 2 The adhesive sheet 2 shown has a structure in which an adhesive layer 21 is provided on one side 10A (non-peelable) of a substrate 10. For the adhesive sheet 2, the other side 10B of the substrate 10 becomes a peeling side, and when the adhesive sheet 2 is rolled up, the adhesive layer 21 abuts against the other side 10B, and the surface (adhesive surface) 21A of the adhesive layer is protected by the other side 10B of the substrate 10.

[0084] Figure 3 , Figure 4 This is an example of the structure of a double-sided adhesive type PSA sheet with a substrate (double-sided PSA sheet with a substrate). Figure 3The adhesive sheet 3 shown has the following structure: an adhesive layer (first adhesive layer) 21 and an adhesive layer (second adhesive layer) 22 are respectively provided on the first surface 10A and the second surface 10B (both of which are non-releasable) of the substrate 10, and the surface of the first adhesive layer 21 (first adhesive surface) and the surface of the second adhesive layer 22 (second adhesive surface) are respectively protected by release liners 31 and 32, at least the side of the adhesive layer serving as the release surface. Figure 4 The adhesive sheet 4 shown has the following structure: a first adhesive layer 21 and a second adhesive layer 22 are respectively provided on the first surface 10A and the second surface 10B (both of which are non-peelable) of the substrate 10, and the surface (first adhesive surface) of the first adhesive layer 21 is protected by a release liner 31 whose two surfaces are release surfaces. For the adhesive sheet 4, by rolling the adhesive sheet 4 so that the surface (second adhesive surface) of the second adhesive layer 22 abuts against the back side of the release liner 31, a structure in which the second adhesive surface is also protected by the release liner 31 can be formed.

[0085] Figure 5 , Figure 6 This is an example of the structure of a double-sided adhesive PSA sheet without a substrate (double-sided PSA sheet without a substrate). Figure 5 The illustrated PSA sheet 5 has a structure in which one surface (first PSA surface) 21A and the other surface (second PSA surface) 21B of a PSA layer 21 without a substrate are protected by release liners 31 and 32 respectively, at least the PSA layer side of which serves as a release surface. Figure 6 The adhesive sheet 6 shown has a structure in which one surface (first adhesive surface) 21A of the adhesive layer 21 is protected by a release liner 31 whose two sides serve as release surfaces. If it is rolled up, the other surface (second adhesive surface) 21B of the adhesive layer 21 abuts against the back side of the release liner 31, thereby forming a structure in which the other side 21B is also protected by the release liner 31.

[0086] A double-sided PSA sheet without a substrate or with a substrate can be used as a single-sided PSA sheet with a substrate by bonding a non-releasable substrate to one of the adhesive surfaces.

[0087] Before use (before attachment to an adherend), the pressure-sensitive adhesive sheet may be, for example, Figures 1 to 6 The form of the adhesive sheet with a release liner in which the adhesive surface is protected by a release liner as shown. As the release liner, there is no particular limitation, for example, a release liner on which the surface of a liner substrate such as a resin film or paper has been subjected to a release treatment, a release liner formed of a low-adhesive material such as a fluorine-based polymer (polytetrafluoroethylene, etc.), a polyolefin-based resin (polyethylene, polypropylene, etc.), etc. can be used. In the above-mentioned release treatment, for example, a release treatment agent such as a polysilicone system or a long-chain alkyl system can be used. In some methods, a resin film subjected to a release treatment can be preferably used as the release liner.

[0088] In the case where the adhesive sheet disclosed in this specification is in the form of a double-sided adhesive sheet with a substrate or a double-sided adhesive sheet without a substrate, the adhesive constituting the first adhesive surface (first adhesive) and the adhesive constituting the second adhesive surface (second adhesive) may be of the same composition or of different compositions. For example, a double-sided adhesive sheet without a substrate having different compositions of the first adhesive surface and the second adhesive surface may be realized by directly (without a substrate) laminating two or more adhesive layers of different compositions with a multilayer structure.

[0089] In some embodiments of the adhesive sheet disclosed in this specification, the adhesive sheet has an adhesive surface composed of an adhesive layer (active energy ray curable adhesive layer) having active energy ray curability. The adhesive sheet involved in some other embodiments has an adhesive surface composed of an adhesive layer (non-active energy ray curable adhesive layer) that does not have active energy ray curability. In the case of a double-sided adhesive sheet having a first adhesive surface and a second adhesive surface, the first adhesive surface and the second adhesive surface can both be adhesive surfaces composed of active energy ray curable adhesive layers, or can both be adhesive surfaces composed of non-active energy ray curable adhesive layers, or can be an adhesive surface composed of an active energy ray curable adhesive layer on one side and an adhesive surface composed of a non-active energy ray curable adhesive layer on the other side. The adhesive sheet disclosed in this specification can preferably be implemented in the following form: a single-sided adhesive sheet with a substrate having at least one adhesive surface composed of an active energy ray curable adhesive layer or a non-active energy ray curable adhesive layer, a double-sided adhesive sheet with a substrate, or a double-sided adhesive sheet without a substrate. Among them, a single-sided PSA sheet with a substrate having an adhesive surface composed of an active energy ray-curable PSA layer or a non-active energy ray-curable PSA layer is preferred.

[0090] <Adhesive layer>

[0091] The adhesive layer (for example, active energy ray curable adhesive layer) constituting the adhesive surface of the adhesive sheet disclosed in this specification can be an adhesive layer composed of one or more adhesives selected from various known adhesives such as acrylic adhesives, rubber adhesives (natural rubber, synthetic rubber, their mixed systems, etc.), polysiloxane adhesives, polyester adhesives, urethane adhesives, polyether adhesives, polyamide adhesives, fluorine adhesives, etc. Here, the so-called acrylic adhesive refers to an adhesive with an acrylic polymer as the base polymer. The same meaning applies to other adhesives such as rubber adhesives.

[0092] It should be noted that, in this specification, the so-called "base polymer" of the adhesive refers to the main component of the polymer contained in the adhesive. In addition, in this specification, the so-called "main component" refers to the component contained in an amount exceeding 50% by weight unless otherwise specified.

[0093] (Acrylic adhesive layer)

[0094] In some embodiments of the adhesive sheet disclosed in this specification, the adhesive layer may be an acrylic adhesive layer containing an acrylic adhesive as a main component. In an adhesive sheet having an acrylic adhesive layer, both an adhesive property suitable for wafer processing and light peelability based on water peeling can be suitably achieved. The acrylic adhesive layer is also preferred from the viewpoint of easily imparting active energy ray curing properties described later.

[0095] As an acrylic adhesive, for example, a polymer containing a monomer raw material containing an alkyl (meth)acrylate or an acrylic polymer that is a modified product thereof obtained by chemical modification or the like is preferably used as a base polymer. As a constituent component of the above-mentioned monomer raw material, an alkyl (meth)acrylate having a linear or branched alkyl group with a carbon number of 1 to 20 at the ester terminal can be preferably used. Hereinafter, an alkyl (meth)acrylate having an alkyl group with a carbon number of X to Y at the ester terminal is sometimes represented as “alkyl (meth)acrylate C X-Y Alkyl esters". From the perspective of easily obtaining adhesive properties suitable for wafer processing applications, (meth) acrylic acid C 1-20 Alkyl esters, preferably (meth) acrylic acid C 1-14 (For example, C 1-12 ) alkyl ester. In addition, as acrylic acid C 1-20 Alkyl ester, preferably acrylic acid C 1-20 (For example, C 1-14 , typically C 1-12 ) alkyl esters.

[0096] As (meth)acrylic acid C 1-20Specific non-limiting examples of the alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. These (meth) alkyl acrylates can be used alone or in combination of two or more. Preferred (meth) alkyl acrylates include ethyl acrylate (EA), n-butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), and lauryl acrylate (LA). In some embodiments, the monomer raw material preferably includes at least one of EA, BA, 2EHA, and LA, more preferably includes at least one of EA, BA, and 2EHA, and further preferably includes at least one of BA and 2EHA.

[0097] In order to easily achieve a balance of properties, in some embodiments, (meth) acrylic acid C 1-20 The proportion of alkyl ester in the above-mentioned monomer raw material is usually preferably 40% by weight or more, preferably more than 50% by weight, for example, 55% by weight or more, 60% by weight or more, 65% by weight or more, or 70% by weight or more. 1-20 The proportion of the alkyl ester is usually preferably 99.9% by weight or less, can be 99% by weight or less, or can be 98% by weight or less. From the perspective of easily forming an adhesive sheet suitable for light peeling based on supplying an aqueous peeling liquid to the peeling front of the adherend, in some embodiments, the (meth) acrylic acid C in the above-mentioned monomer raw material 1-20 The proportion of the alkyl ester may be, for example, 95% by weight or less, 85% by weight or less, less than 80% by weight, or 70% by weight or less.

[0098] In some preferred embodiments, the above-mentioned alkyl (meth)acrylate comprises an alkyl (meth)acrylate A1 having an alkyl group with a carbon number of 9 or less at the end of the ester (i.e., alkyl (meth)acrylate C 1-9Alkyl ester). (Meth) alkyl acrylate A1 can be used alone or in combination of two or more. By limiting the length of the side chain alkyl structure as described above, there is a tendency to obtain high cohesion (which can highly prevent residual glue). For example, in the structure with a carbon-carbon double bond in the side chain (typically, the side chain end) of the polymer, the length of the side chain alkyl is limited, and thus, during the curing treatment, the reaction of the carbon-carbon double bond can proceed smoothly. In addition, because the length of the side chain alkyl is limited, therefore, for an adhesive sheet having an adhesive layer comprising a polymer obtained from the monomer, a stripping method of supplying water or other aqueous stripping liquids to the stripping front of the adherend can be utilized to efficiently strip it from the adherend.

[0099] The proportion of the (meth) alkyl ester A1 in the above-mentioned monomer raw material as a whole is preferably about 30% by weight or more. From the perspective of better presenting the effect of the (meth) alkyl ester A1, it is preferably about 40% by weight or more, and more preferably about 55% by weight or more. In some embodiments, the proportion of the above-mentioned alkyl (meth) acrylate A1 can be, for example, about 65% by weight or more, about 75% by weight or more, or about 80% by weight or more. In some other embodiments, the proportion of the above-mentioned alkyl (meth) acrylate A1 can be, for example, about 85% by weight or more, about 90% by weight or more, or about 95% by weight or more. There is no particular upper limit on the proportion of the alkyl (meth) acrylate A1 in the above-mentioned monomer raw material. Generally, it is suitable to be less than 99.5% by weight, for example, less than 99% by weight. In some embodiments, for example, from the viewpoint of well presenting the effect of the above-mentioned carbon-carbon double bond in an adhesive layer comprising a polymer having a carbon-carbon double bond, the proportion of the above-mentioned (meth)acrylate A1 in the above-mentioned monomer raw material as a whole is preferably about 95 wt % or less, more preferably about 90 wt % or less, can be about 85 wt % or less, can be about 75 wt % or less, can be about 70 wt % or less.

[0100] The proportion of the alkyl (meth)acrylate A1 in the total alkyl (meth)acrylate is preferably about 50% by weight or more, preferably about 70% by weight or more, more preferably about 80% by weight or more, about 90% by weight or more, about 95% by weight or more, or about 99% by weight or more, from the viewpoint of well exhibiting the effect of the alkyl (meth)acrylate A1. The upper limit of the proportion of the alkyl (meth)acrylate A1 in the total alkyl (meth)acrylate is 100% by weight.

[0101] In some embodiments, the above-mentioned (meth) acrylate alkyl ester A1 may include one or more (meth) acrylate alkyl ester A3 having an alkyl group with a carbon number of less than 7 at the end of the ester. For an adhesive comprising a polymer obtained from a monomer raw material comprising an (meth) acrylate alkyl ester A3, it is easy to provide an adhesive sheet that can be efficiently peeled off by supplying a peeling liquid such as water to the peeling front of the peeling from the adherend. In addition, for an active energy ray-curable adhesive comprising a polymer obtained from a monomer raw material comprising an (meth) acrylate alkyl ester A3, the curing reaction based on the irradiation of active energy rays can be carried out well. From such a viewpoint, the carbon number of the alkyl group in the (meth) acrylate alkyl ester A3 is preferably 6 or less, more preferably 4 or less, and can be 3 or less or 2 or less. In addition, the carbon number of the alkyl group in the (meth) acrylate alkyl ester A3 can be 1 or more, and from the viewpoint of adhesion to the adherend, it is preferably 2 or more.

[0102] In the embodiment in which the above-mentioned monomer raw material contains the (meth) alkyl ester A3, the proportion of the (meth) alkyl ester A3 in the whole monomer raw material can be, for example, about 1% by weight or more, usually, preferably about 5% by weight or more, and from the viewpoint of well exhibiting the effect of the (meth) alkyl ester A3, preferably about 20% by weight or more, more preferably about 30% by weight or more, further preferably about 40% by weight or more, particularly preferably about 50% by weight or more, for example, it can be 60% by weight or more, can be about 70% by weight or more, can be about 80% by weight or more, can be about 90% by weight or more. The upper limit of the proportion of the (meth) alkyl ester A3 in the whole monomer raw material is not particularly limited, usually, it is preferably about 99% by weight or less, for example, it can be 90% by weight or less. In some embodiments, for example, from the viewpoint of well showing the effect of the carbon-carbon double bond in the adhesive layer containing the polymer having the carbon-carbon double bond, the proportion of the alkyl (meth)acrylate A3 in the whole monomer raw material is preferably about 80 wt % or less, more preferably about 70 wt % or less, and further preferably about 60 wt % or less. The above embodiment may be, for example, a method of introducing a reactive group used for curing treatment or a functional group serving as a crosslinking point into the polymer.

[0103] The proportion of the alkyl (meth)acrylate A3 in the total alkyl (meth)acrylate is preferably about 5% by weight or more, and from the viewpoint of well exhibiting the effect of the alkyl (meth)acrylate A3, it is preferably about 20% by weight or more, more preferably about 35% by weight or more, further preferably about 45% by weight or more, and particularly preferably about 55% by weight or more, for example, about 65% by weight or more, about 75% by weight or more, about 85% by weight or more, or about 90% by weight or more. The upper limit of the proportion of the alkyl (meth)acrylate A3 in the total alkyl (meth)acrylate is 100% by weight, for example, it can be about 98% by weight or less. In some embodiments, for example, when the alkyl (meth)acrylate A2 described later is used in combination with the alkyl (meth)acrylate A3, from the viewpoint of exhibiting its effect well, the proportion of the alkyl (meth)acrylate A3 in the total alkyl (meth)acrylate may be, for example, about 90% by weight or less, about 85% by weight or less, about 75% by weight or less, about 60% by weight or less, about 45% by weight or less, about 30% by weight or less, or about 15% by weight or less. The alkyl (meth)acrylate A3 may not be used.

[0104] In some embodiments, the above-mentioned alkyl (meth)acrylate may contain an alkyl (meth)acrylate A2 having an alkyl group with 7 or more carbon atoms at the ester end as the above-mentioned alkyl (meth)acrylate A1, or as a monomer different from the alkyl (meth)acrylate A1. In the case of using the alkyl (meth)acrylate A2, it may be advantageous, for example, from the viewpoint of adhesion to the adherend. The number of carbon atoms of the alkyl group in the alkyl (meth)acrylate A2 is preferably 8 or more, and may be 9 or more. In addition, from the viewpoint of adhesive properties such as adhesive strength, the number of carbon atoms of the alkyl group in the alkyl (meth)acrylate A2 is preferably 14 or less, more preferably 12 or less, further preferably 10 or less, for example 9 or less, and may be less than 9.

[0105] In the embodiment in which the above-mentioned monomer raw material contains the (meth) alkyl acrylate A2, the proportion of the (meth) alkyl acrylate A2 in the whole monomer raw material can be, for example, about 1% by weight or more, usually, preferably about 5% by weight or more, and from the viewpoint of better exhibiting the effect of the (meth) alkyl acrylate A2, preferably about 20% by weight or more, more preferably about 30% by weight or more, further preferably about 40% by weight or more, particularly preferably about 50% by weight or more, for example, it can be 60% by weight or more, can be about 70% by weight or more, can be about 80% by weight or more, can be about 90% by weight or more. The upper limit of the proportion of the (meth) alkyl acrylate A2 in the whole monomer raw material is not particularly limited, usually, it is preferably about 99.5% by weight or less, for example, it can be about 99% by weight or less. In some embodiments, for example, from the viewpoint of well presenting the effect of the above-mentioned carbon-carbon double bond in an adhesive layer comprising a polymer having a carbon-carbon double bond, the proportion of the above-mentioned (meth)acrylate A2 in the above-mentioned monomer raw material as a whole is preferably about 95 wt % or less, can be about 90 wt % or less, can be about 85 wt % or less, can be about 75 wt % or less, can be about 70 wt % or less.

[0106] The proportion of the (meth)acrylic acid alkyl ester A2 in the total (meth)acrylic acid alkyl ester contained in the above-mentioned monomer raw material is preferably about 5% by weight or more. From the viewpoint of well showing the effect of the (meth)acrylic acid alkyl ester A2, it is preferably about 20% by weight or more, more preferably about 35% by weight or more, and further preferably about 45% by weight or more. For example, it can be about 55% by weight or more, about 65% by weight or more, about 75% by weight or more, about 85% by weight or more, about 90% by weight or more, or about 95% by weight or more. The upper limit of the proportion of the (meth)acrylic acid alkyl ester A2 in the total (meth)acrylic acid alkyl ester is 100% by weight. In some embodiments, for example, when the alkyl (meth)acrylate A3 is used in combination with the alkyl (meth)acrylate A2, from the viewpoint of well exhibiting its effect, the proportion of the alkyl (meth)acrylate A2 in the total alkyl (meth)acrylate may be, for example, about 95% by weight or less, about 90% by weight or less, about 80% by weight or less, about 70% by weight or less, about 60% by weight or less, about 45% by weight or less, about 30% by weight or less, about 20% by weight or less, about 10% by weight or less, or about 5% by weight or less. The alkyl (meth)acrylate A2 may not be used.

[0107] The monomer raw material that can be used in the synthesis of acrylic polymers can also include a secondary monomer that is copolymerizable with the above-mentioned (meth) alkyl acrylate. The secondary monomer can help introduce crosslinking points into the acrylic polymer or improve the cohesive force of the acrylic polymer. In addition, for example, for the monomer raw material that can be used in the synthesis of a polymer having a carbon-carbon double bond, it is preferred to use a monomer having a functional group (hereinafter also referred to as "functional group A") that can react with a functional group (hereinafter also referred to as "functional group B") of a monomer containing a carbon-carbon double bond described later as the secondary monomer.

[0108] As the secondary monomer, for example, the following functional group-containing monomers may be used alone or in combination of two or more.

[0109] Monomers containing hydroxyl groups: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate; unsaturated alcohols such as vinyl alcohol and allyl alcohol; ether compounds such as 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether.

[0110] Carboxyl group-containing monomers: for example, ethylenically unsaturated monocarboxylic acids such as acrylic acid (AA), methacrylic acid (MAA), crotonic acid, isocrotonic acid, etc.; ethylenically unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, citraconic acid, etc.

[0111] Monomers containing anhydride groups: for example, maleic anhydride, itaconic anhydride.

[0112] Monomers having a ring containing a nitrogen atom: for example, N-vinyl-2-pyrrolidone, methyl-N-vinylpyrrolidone, vinylpyridine, vinylpyrazine, vinylpyrimidine, N-vinylpiperidone, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazine-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, N-(meth)acryloylmorpholine, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, and the like.

[0113] Monomers containing amide groups: for example, (meth)acrylamide; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di(n-butyl) (meth)acrylamide, N,N-di(tert-butyl) (meth)acrylamide and the like N,N-dialkyl (meth)acrylamide; N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-n-butyl (meth)acrylamide and the like N-alkyl (meth)acrylamide; N-vinyl carboxylic acid amides such as N-vinyl acetamide; Monomers having hydroxyl groups and amide groups, for example, N-(2-hydroxyethyl) (methyl)acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, N-(1-hydroxypropyl)(meth)acrylamide, N-(3-hydroxypropyl)(meth)acrylamide, N-(2-hydroxybutyl)(meth)acrylamide, N-(3-hydroxybutyl)(meth)acrylamide, N-(4-hydroxybutyl)(meth)acrylamide, etc.; monomers having an alkoxy group and an amide group, for example, N-alkoxyalkyl(meth)acrylamide such as N-methoxymethyl(meth)acrylamide, N-methoxyethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide; N,N-dialkylaminoalkyl(meth)acrylamide such as N,N-dimethylaminopropyl(meth)acrylamide, etc.

[0114] Monomers containing amino groups: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.

[0115] Monomers having a succinimide skeleton include, for example, N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyhexamethylenesuccinimide.

[0116] Maleimides: for example, N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, etc.

[0117] Itaconimides: for example, N-methyl itaconimide, N-ethyl itaconimide, N-butyl itaconimide, N-octyl itaconimide, N-2-ethylhexyl itaconimide, N-cyclohexyl itaconimide, N-lauryl itaconimide and the like.

[0118] Epoxy group-containing monomers: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, and allyl glycidyl ether.

[0119] Monomers containing cyano groups: for example, acrylonitrile and methacrylonitrile.

[0120] Monomers containing a ketone group: for example, diacetone (meth)acrylamide, diacetone (meth)acrylate, vinyl methyl ketone, vinyl ethyl ketone, allyl acetoacetate, vinyl acetoacetate.

[0121] Monomers containing alkoxysilyl groups: for example, (meth)acrylates containing alkoxysilyl groups such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, and the like; and vinyl compounds containing alkoxysilyl groups such as vinyltrimethoxysilane and vinyltriethoxysilane.

[0122] Monomers containing amino groups: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.

[0123] Monomers having an epoxy group: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, and allyl glycidyl ether.

[0124] Monomers containing sulfonic acid groups or phosphoric acid groups: for example, styrene sulfonic acid, allyl sulfonic acid, sodium vinyl sulfonate, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl (meth)acrylate, (meth)acryloyloxynaphthalenesulfonic acid, 2-hydroxyethyl acryloyl phosphate, etc.

[0125] Monomers containing an isocyanate group: for example, 2-isocyanateethyl (meth)acrylate, (meth)acryloyl isocyanate, and m-isopropenyl-α,α-dimethylbenzyl isocyanate.

[0126] The amount of the above-mentioned monomer containing functional groups can be appropriately selected in a manner that can realize desired cohesive force, and is not particularly limited. Usually, from the viewpoint of realizing cohesive force and other characteristics (such as adhesion) well-balanced simultaneously, the amount of the monomer containing functional groups (when using more than 2 kinds of monomers containing functional groups, their total amount) is usually suitable for more than 0.1% by weight of the overall monomer raw material, preferably more than 0.3% by weight, for example, more than 1% by weight. In addition, the amount of the monomer containing functional groups can be, for example, less than 50% by weight of the overall monomer raw material, preferably less than 40% by weight, for example, less than 35% by weight, can be less than 30% by weight, can be less than 25% by weight, can be less than 20% by weight.

[0127] In some ways, the above-mentioned monomer raw material may include a monomer containing a hydroxyl group as the above-mentioned monomer containing a functional group. The amount used in the case of using a monomer containing a hydroxyl group is not particularly limited, for example, it can be more than 0.01% by weight of the overall monomer raw material, it can be more than 0.1% by weight, it can be more than 0.5% by weight, it can be more than 1% by weight, it can be more than 5% by weight or more than 10% by weight. In some ways, the amount of the monomer containing a hydroxyl group can be, for example, less than 50% by weight of the overall monomer raw material, from the viewpoint of suppressing the water absorption of the adhesive, it is usually suitable to be less than 40% by weight, it can be less than 30% by weight, it can be less than 25% by weight, it can be less than 20% by weight. In addition, in some ways, the amount of the monomer containing a hydroxyl group can be less than 15% by weight of the overall monomer raw material, it can be less than 10% by weight, it can be less than 5% by weight. Alternatively, a monomer containing a hydroxyl group may not be used.

[0128] In some embodiments, the above-mentioned monomer raw material may include a monomer containing a carboxyl group as the above-mentioned monomer containing a functional group. The proportion of the monomer containing a carboxyl group in the overall monomer raw material that can be used in the synthesis of acrylic polymers can be, for example, less than 15% by weight, less than 10% by weight, and from the viewpoint of water absorption inhibition of the adhesive layer during wafer processing, it is preferably less than 7% by weight, less than 5% by weight, less than 3% by weight, less than 2% by weight, less than 1% by weight, less than 0.5% by weight, and less than 0.1% by weight. The above-mentioned monomer raw material may not substantially include a monomer containing a carboxyl group. Here, the so-called substantially not including a monomer containing a carboxyl group means that at least a monomer containing a carboxyl group is not intentionally used. For example, the following composition can be preferably adopted: in the monomer raw material that can be used in the preparation of a polymer having a carbon-carbon double bond in a side chain, the proportion of a carboxyl monomer is limited as described above.

[0129] In some embodiments, the monomer raw material may include a monomer having a nitrogen atom as the monomer containing a functional group. By using a monomer having a nitrogen atom, a moderate polarity can be imparted to the adhesive. This can be advantageous for the realization of a lightly peeled adhesive sheet suitable for the supply of an aqueous peeling solution such as water. As a preferred example of a monomer having a nitrogen atom, a monomer having a ring containing a nitrogen atom can be cited. As a monomer having a ring containing a nitrogen atom, from the viewpoints of compatibility, N-vinyl compounds such as N-vinyl-2-pyrrolidone (N-vinyl cyclic amides, etc.), N-(methyl)acryloyl morpholine and other N-(methyl)acryloyl compounds can be preferably used.

[0130] There is no particular restriction on the amount used when using a monomer with a nitrogen atom, for example, it can be more than 1% by weight of the entire monomer raw material, it can be more than 2% by weight, it can be more than 3% by weight, it can be more than 5% by weight, it can be more than 7% by weight. From the viewpoint of obtaining a higher effect, in some ways, the amount of the monomer with a nitrogen atom can be more than 10% by weight of the entire monomer raw material, it can be more than 15% by weight, it can be more than 20% by weight. In addition, from the viewpoint of easy acquisition of the balance of characteristics, the amount of the monomer with a nitrogen atom is usually suitable for the entire monomer raw material, for example, less than 40% by weight, it can be less than 35% by weight, it can be less than 30% by weight, it can be less than 25% by weight. In some ways, the amount of the monomer with a nitrogen atom can be less than 20% by weight of the entire monomer raw material, for example, less than 15% by weight, it can be less than 10% by weight, it can be less than 5% by weight. Alternatively, a monomer with a nitrogen atom may not be used.

[0131] When the above-mentioned monomer raw material is used for the preparation of a polymer with a carbon-carbon double bond, as a secondary monomer, it is preferred to use a monomer containing a functional group (functional group A) that can react with a functional group (functional group B) of a compound with a carbon-carbon double bond described later. In the above case, the type of the monomer containing the functional group can be determined according to the type of the above-mentioned compound. As a secondary monomer with functional group A, for example, a monomer containing a hydroxyl group, a monomer containing a carboxyl group, a monomer containing an epoxy group, a monomer containing an isocyanate group, and a monomer containing a hydroxyl group are preferably used, and a monomer containing a hydroxyl group is particularly preferred. By using a monomer containing a hydroxyl group as a secondary monomer, the acrylic polymer is provided with a hydroxyl group. In contrast, by using a monomer containing an isocyanate group as a compound with a carbon-carbon double bond, the hydroxyl group (functional group A) of the above-mentioned acrylic polymer reacts with the isocyanate group (functional group B) of the above-mentioned compound, and the carbon-carbon double bond from the above-mentioned compound can be introduced into the acrylic polymer.

[0132] In addition, when the secondary monomer is used for the purpose of reacting with a compound having a carbon-carbon double bond, from the viewpoint of easily obtaining an adhesive layer suitable for water peeling, the amount of the secondary monomer (preferably a monomer containing a hydroxyl group) is preferably about 1% by weight or more of the total monomer raw material, preferably about 5% by weight or more, more preferably about 10% by weight or more, further preferably about 12% by weight or more, for example, about 14% by weight or more. In addition, from the viewpoint of maintaining good adhesive properties such as adhesion, the amount of the secondary monomer is preferably about 40% by weight or less of the total monomer raw material, preferably about 30% by weight or less, more preferably about 20% by weight or less, for example, about 15% by weight or less.

[0133] The monomer raw material that can be used for preparing the acrylic polymer may contain a secondary monomer (hereinafter also referred to as a copolymerizable monomer) other than the above-mentioned functional group-containing monomer for the purpose of improving the cohesive force of the acrylic polymer.

[0134] Specific non-limiting examples of the copolymerizable monomer include the following.

[0135] Alkyl group-containing monomers: for example, alkoxyalkyl (meth)acrylates (alkoxyalkyl (meth)acrylates) such as 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, and 2-ethoxyethyl (meth)acrylate; alkoxy (poly)alkylene glycol (meth)acrylates such as methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate.

[0136] Vinyl esters: for example, vinyl acetate, vinyl propionate, etc.

[0137] Vinyl ethers: For example, vinyl alkyl ethers such as methyl vinyl ether and ethyl vinyl ether.

[0138] Aromatic vinyl compounds: for example, styrene, α-methylstyrene, vinyltoluene, etc.

[0139] Olefins: for example, ethylene, butadiene, isoprene, isobutylene, etc.

[0140] (Meth)acrylates having an alicyclic hydrocarbon group: for example, (meth)acrylates having an alicyclic hydrocarbon group such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and adamantyl (meth)acrylate.

[0141] (Meth)acrylates containing an aromatic ring: for example, aryl (meth)acrylates such as phenyl (meth)acrylate, aryloxyalkyl (meth)acrylates such as phenoxyethyl (meth)acrylate, and arylalkyl (meth)acrylates such as benzyl (meth)acrylate.

[0142] Also, (meth)acrylates containing heterocycles such as tetrahydrofurfuryl (meth)acrylate, halogen atom-containing monomers such as vinyl chloride and fluorine-containing (meth)acrylates, organosiloxane chain-containing monomers such as polysiloxane (meth)acrylates, (meth)acrylates obtained from terpene compound derivative alcohols, and the like.

[0143] Such copolymerizable monomers can be used alone or in combination of two or more. The amount of the above-mentioned other copolymerizable monomers is not particularly limited and can be appropriately selected according to the purpose and use. For example, it is preferably less than 20% by weight (e.g., 2 to 20% by weight, typically 3 to 10% by weight) of all monomer raw materials of the acrylic polymer.

[0144] In a preferred embodiment, from the viewpoint of suppressing gelation, the total ratio of the alkoxyalkyl (meth)acrylate and the alkoxypolyalkylene glycol (meth)acrylate is preferably limited to less than 20% by weight. The total ratio of the alkoxyalkyl (meth)acrylate and the alkoxypolyalkylene glycol (meth)acrylate is more preferably less than 10% by weight, further preferably less than 3% by weight, and particularly preferably less than 1% by weight. In one embodiment, the monomer raw material does not substantially contain the alkoxyalkyl (meth)acrylate and the alkoxypolyalkylene glycol (meth)acrylate (the content is 0 to 0.3% by weight).

[0145] Similarly, in one embodiment, the monomer raw material may contain a monomer containing an alkoxy group at a ratio of less than 20% by weight, or may not contain a monomer containing an alkoxy group. The amount of the monomer containing an alkoxy group in the monomer raw material is preferably less than 10% by weight, more preferably less than 3% by weight, and further preferably less than 1% by weight. In a particularly preferred embodiment, the monomer raw material does not substantially contain a monomer containing an alkoxy group (the content is 0 to 0.3% by weight).

[0146] The method for polymerizing the monomer raw material is not particularly limited, and various polymerization methods known as the synthesis methods of acrylic polymers such as solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization can be appropriately adopted. For example, solution polymerization can be preferably adopted. As a monomer supply method when performing solution polymerization, a method of charging all monomer raw materials at once, a continuous supply (drip) method, a batch supply (drip) method, etc. can be appropriately adopted. The solvent (polymerization solvent) used in the solution polymerization can be appropriately selected from the existing known organic solvents. For example, any one solvent selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); esters such as ethyl acetate and butyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropyl alcohol (for example, monohydric alcohols having 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone; etc., or a mixed solvent of two or more can be used. The polymerization temperature can be appropriately selected according to the type of monomer and solvent used, the type of polymerization initiator, etc., and can be, for example, about 20°C to 120°C (typically, 40°C to 80°C). By solution polymerization, a polymerization reaction liquid in the form of a polymer of a monomer raw material dissolved in a polymerization solvent can be obtained. The adhesive composition for forming an adhesive layer can preferably be manufactured using the above-mentioned polymerization reaction liquid. The method for manufacturing an adhesive composition using the above-mentioned polymerization reaction liquid may, for example, include a step of chemically modifying the polymer contained in the above-mentioned polymerization reaction liquid by introducing a carbon-carbon double bond.

[0147] During polymerization, known or customary thermal polymerization initiators and photopolymerization initiators can be used according to the polymerization method, polymerization mode, etc. As examples of thermal polymerization initiators, azo polymerization initiators, peroxide-based initiators, redox-based initiators based on a combination of peroxides and reducing agents, substituted ethane-based initiators, etc. can be used. As examples of photopolymerization initiators, α-ketol-based photoinitiators, acetophenone-based photoinitiators, benzoin ether-based photoinitiators, ketal-based photoinitiators, aromatic sulfonyl chloride-based photoinitiators, photoactive oxime-based photoinitiators, benzophenone-based photoinitiators, thioxanthone-based photoinitiators, acylphosphine oxide-based photoinitiators, etc. can be cited. The polymerization initiator can be used alone or in combination of two or more.

[0148] The amount of the polymerization initiator used may be a normal amount, for example, it may be selected from a range of about 0.005 to 1 part by weight (typically, 0.01 to 1 part by weight) relative to 100 parts by weight of the total monomer raw materials. In addition, when the polymerization initiator is also used as a photoinitiator, the amount of the polymerization initiator used may be set in consideration of this.

[0149] In the above polymerization, various chain transfer agents known in the art (also referred to as molecular weight regulators or polymerization degree regulators) may be used as needed. As chain transfer agents, thiols such as n-dodecyl mercaptan, tert-dodecyl mercaptan, thioglycolic acid, and α-thioglycerol may be used. Alternatively, chain transfer agents not containing sulfur atoms (non-sulfur chain transfer agents) may be used. Specific examples of non-sulfur chain transfer agents include anilines such as N,N-dimethylaniline and N,N-diethylaniline; terpenoids such as α-pinene and terpinolene; styrenes such as α-methylstyrene and α-methylstyrene dimer; compounds having a benzylidene group such as dibenzylideneacetone, cinnamyl alcohol, and cinnamaldehyde; hydroquinones such as hydroquinone and naphthalenediol; quinones such as benzoquinone and naphthoquinone; olefins such as 2,3-dimethyl-2-butene and 1,5-cyclooctadiene; alcohols such as phenol, benzyl alcohol, and allyl alcohol; benzyl hydrogens such as diphenylbenzene and triphenylbenzene; and the like.

[0150] The chain transfer agent may be used alone or in combination of two or more. When a chain transfer agent is used, the amount used may be, for example, about 0.01 to 1 part by weight relative to 100 parts by weight of the monomer raw material. The technology disclosed in this specification may also be preferably implemented without using a chain transfer agent.

[0151] The molecular weight of the acrylic polymer is not particularly limited and can be set within an appropriate range according to the required performance. The weight average molecular weight (Mw) of the acrylic polymer is generally about 10×10 4 Above (e.g. 20×10 4 From the perspective of achieving cohesive force and adhesive force in a well-balanced manner, it is preferably greater than 30×10 4 , preferably about 40×10 4 Above, it can be about 50×10 4 Above, it can be about 55×10 4 The upper limit of the Mw of the acrylic polymer is not particularly limited. From the viewpoint of the coating properties of the adhesive composition, the Mw of the acrylic polymer is generally preferably about 500×10 4 Below, for example, it can be about 150×10 4 Below, it can be about 75×10 4 The above-mentioned Mw may be the Mw of the acrylic polymer in either the PSA composition or the PSA layer.

[0152] Here, Mw refers to a value obtained by gel permeation chromatography (GPC) in terms of standard polystyrene. As a GPC apparatus, for example, a machine model "HLC-8320GPC" (column: TSK gel GMH-H (S), manufactured by Tosoh Corporation) can be used. The same applies to the examples described below.

[0153] The acrylic adhesive layer may further contain polymers other than acrylic polymers as secondary polymers as needed. As the above-mentioned secondary polymers, polymers other than acrylic polymers among the various polymers cited as polymers that can be contained in the adhesive layer can be cited as preferred examples. In the case where the adhesive layer disclosed in this specification is an acrylic adhesive layer that contains not only acrylic polymers but also secondary polymers, the content of the secondary polymer is preferably less than 100 parts by weight, preferably 50 parts by weight or less, more preferably 30 parts by weight or less, and further preferably 10 parts by weight or less relative to 100 parts by weight of the acrylic polymer. The content of the secondary polymer can be 5 parts by weight or less, and can be 1 part by weight or less relative to 100 parts by weight of the acrylic polymer. The technology disclosed in this specification can be preferably implemented, for example, by 99.5 to 100% by weight of the polymer contained in the adhesive layer being an acrylic polymer.

[0154] (Adhesive layer other than acrylic adhesive layer)

[0155] The adhesive layer constituting the adhesive surface in the adhesive sheet disclosed in this specification may be an adhesive layer having a polymer other than an acrylic polymer as a base polymer, that is, an adhesive layer other than acrylic. For the adhesive layer other than acrylic, in addition to the base polymer, a secondary polymer other than the base polymer may be further included as needed. In this case, the content of the secondary polymer in the adhesive layer other than acrylic can be selected from the above-mentioned contents exemplified as the content of the secondary polymer in the acrylic adhesive layer. The adhesive layer other than acrylic may be an adhesive layer containing an acrylic polymer as a secondary polymer.

[0156] (Glass transition temperature)

[0157] The glass transition temperature (Tg) of the base polymer (e.g., acrylic polymer) of the adhesive layer constituting the adhesive surface is preferably about 15°C or less. In some embodiments, from the viewpoint of adhesion to the adherend (e.g., the ability to follow the surface shape of the adherend), the above Tg is suitably 10°C or less, preferably 0°C or less, and may be -10°C or less, or -20°C or less. In addition, from the viewpoint of the cohesiveness of the adhesive and the ease of easy peeling by water peeling, the Tg of the base polymer may be, for example, above -75°C, above -60°C, or above -50°C. In some embodiments, the Tg of the base polymer may be above -45°C, or above -40°C.

[0158] Here, in this specification, the glass transition temperature (Tg) of a polymer refers to the glass transition temperature obtained by the Fox equation based on the composition of the monomer raw materials constituting the polymer. The above-mentioned Fox equation, as shown below, refers to the relationship between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing the monomers constituting the copolymer.

[0159] 1 / Tg=Σ(Wi / Tgi)

[0160] It should be noted that in the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K).

[0161] As the glass transition temperature of the homopolymer used for calculation of Tg, the value described in the known document is used. For example, regarding the monomers listed below, as the glass transition temperature of the homopolymer of the monomer, the following value is used.

[0162]

[0163] Regarding the glass transition temperature of homopolymers of monomers other than those exemplified above, the values ​​described in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) are used. When a plurality of values ​​are described in this document, the highest value is adopted.

[0164] Regarding the monomer whose glass transition temperature of homopolymer is not recorded in the above-mentioned Polymer Handbook, the value obtained by the following measurement method is used (see Japanese Patent Publication No. 2007-51271). Specifically, 100 parts by weight of monomer, 0.2 parts by weight of azobisisobutyronitrile and 200 parts by weight of ethyl acetate as a polymerization solvent are added to a reactor equipped with a thermometer, a stirrer, a nitrogen inlet tube and a reflux condenser, and stirred for 1 hour while circulating nitrogen. The above operation is performed to remove oxygen in the polymerization system, and then the temperature is raised to 63°C and the reaction is carried out for 10 hours. Next, it is cooled to room temperature to obtain a homopolymer solution with a solid content concentration of 33% by weight. Next, the homopolymer solution is cast on a release liner and dried to prepare a test sample (sheet-shaped homopolymer) with a thickness of about 2 mm. The test sample was punched into a disc with a diameter of 7.9 mm, clamped with parallel plates, and a viscoelasticity tester (ARES, manufactured by Rheometrics Inc.) was used to provide shear strain at a frequency of 1 Hz while measuring the viscoelasticity in a shear mode in a temperature range of -70 to 150°C and a heating rate of 5°C / min. The peak temperature of tanδ was taken as the Tg of the homopolymer.

[0165] (Surfactant)

[0166] In some preferred embodiments, the adhesive layer may contain a surfactant. The adhesive layer containing a surfactant can appropriately present the effect of reducing the peeling force by supplying an aqueous stripping solution to the peeling interface with the adherend. Although the reason for this is not particularly restrictive, the following reasons can be considered: the surfactant has a hydrophilic region, and thus, it is preferentially present on the surface of the adhesive layer, and when it comes into contact with the aqueous stripping solution, the peeling force is effectively reduced. As a surfactant, one or more of the known surfactants can be used without particular restrictions. The surfactant is typically preferably contained in the adhesive layer in a free form. As a surfactant, from the aspect of the preparation of the adhesive composition, a surfactant that is liquid at room temperature (about 25°C) can be preferably used.

[0167] There is no particular limitation on the HLB of the surfactant. The HLB of the surfactant may be, for example, 1 or more or 3 or more. The HLB of the surfactant is preferably 5 or more, 6 or more, 8 or more, or 9 or more. As a result, there is a tendency to appropriately exhibit water stripping properties. The HLB of the surfactant is more preferably 10 or more, further preferably 11 or more, further preferably 12 or more, particularly preferably 13 or more, 14 or more, 15 or more, and further 16 or more. By using a surfactant having an HLB in the above range, light stripping properties based on water stripping can be more effectively presented. The upper limit of the above HLB is 20 or less, for example, 18 or less. In some embodiments, for example, from the perspective of compatibility, the HLB of the surfactant may be 16 or less, for example, 15 or less.

[0168] It should be noted that the HLB in this specification is a hydrophile-lipophile balance value proposed by Griffin, which is a value indicating the degree of affinity between a surfactant and water and oil, and a numerical value between 0 and 20 indicates the ratio of hydrophilicity to lipophilicity. The definition of HLB is as described in WC Griffin: J. Soc. Cosmetic Chemists, 1, 311 (1949), Takahashi Etsumin, Nanba Yoshiro, Koike Motoo, Kobayashi Masao, "Surfactant Handbook", 3rd edition, published by Gongxue Booksha, November 25, 1972, p179-182, etc. The surfactant having the above HLB can be selected based on the technical common sense of those skilled in the art with reference to the above references, etc. as needed.

[0169] As the surfactant, known nonionic surfactants, anionic surfactants, cationic surfactants, etc. can be used. Among them, nonionic surfactants are preferred. The surfactant can be used alone or in combination of two or more.

[0170] Examples of nonionic surfactants include polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether and the like; polyoxyethylene alkylphenyl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; polyoxyethylene fatty acid esters such as polyoxyethylene monolaurate, polyoxyethylene monostearate, and polyoxyethylene monooleate; sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, and sorbitan monooleate; Sorbitan fatty acid esters such as polyoxyethylene sorbitan monooleate; polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan triisostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, etc.; polyoxyethylene glyceryl ether fatty acid esters; polyoxyethylene-polyoxypropylene block copolymers; and the like. The nonionic surfactant may be a reactive surfactant having a free radical polymerizable functional group such as acryl, (meth)allyl, vinyl, (meth)acryloyl (for example, a nonionic reactive surfactant such as polyoxyethylene nonyl propenyl phenyl ether). These nonionic surfactants may be used alone or in combination of two or more. From the perspective of the performance stability of the adhesive sheet, it is preferred to use a (non-reactive) nonionic surfactant that does not have such a free radical polymerizable functional group.

[0171] Examples of anionic surfactants include alkyl sulfates such as lauryl sulfate and octadecyl sulfate; fatty acid salts; alkylbenzene sulfonates such as nonylbenzene sulfonate and dodecylbenzene sulfonate; naphthalene sulfonates such as dodecylnaphthalene sulfonate; alkyldiphenyl ether disulfonates such as dodecyldiphenyl ether disulfonates; polyoxyethylene alkyl ether sulfates such as polyoxyethylene octadecyl ether sulfate and polyoxyethylene lauryl ether sulfate; polyoxyethylene alkylphenyl ether sulfates such as polyoxyethylene lauryl phenyl ether sulfate; polyoxyethylene styrenated phenyl ether sulfate; sulfosuccinates such as lauryl sulfosuccinate and polyoxyethylene lauryl sulfosuccinate; polyoxyethylene alkyl ether phosphates; polyoxyethylene alkyl ether acetates; and the like. When the anionic surfactant forms a salt, the salt may be, for example, a metal salt (preferably a monovalent metal salt) such as a sodium salt, a potassium salt, a calcium salt, a magnesium salt, an ammonium salt, an amine salt, or the like. These anionic surfactants may be used alone or in combination of two or more.

[0172] The amount of surfactant used is not particularly limited, and can be set in a manner that the peeling force reduction brought about by supplying an aqueous stripping solution is effectively presented. In some embodiments, the amount of surfactant used can be, for example, about 5 parts by weight or less relative to 100 parts by weight of the base polymer. From the perspective of the bonding reliability relative to the adherend, it is suitable to be about 3 parts by weight or less, preferably less than 2 parts by weight, more preferably less than 1 part by weight, less than 0.8 parts by weight, less than 0.6 parts by weight, less than 0.4 parts by weight, less than 0.2 parts by weight, and less than 0.1 parts by weight. For surfactants with high HLB (for example, more than 5), even if added in small amounts, there is a tendency to easily exert good water stripping properties. In addition, from the perspective of exerting the effect of adding surfactants, in some embodiments, the amount of surfactant relative to 100 parts by weight of the base polymer can be, for example, 0.001 parts by weight or more. From the perspective of more uniformly presenting the peeling force reduction effect brought about by supplying an aqueous stripping solution, it is usually suitable to be 0.01 parts by weight or more, preferably 0.03 parts by weight or more (for example, 0.1 parts by weight or more). In a composition in which water-strippability is important, the amount of the surfactant may be 0.3 parts by weight or more (eg, 0.5 parts by weight or more) based on 100 parts by weight of the base polymer.

[0173] (Crosslinking agent)

[0174] In the adhesive layer (which can be an active energy ray-curable adhesive layer), a crosslinking agent can be used as needed for the purpose of adjusting cohesion. The crosslinking agent can be contained in the adhesive layer in the form after the crosslinking reaction, or in the form before the crosslinking reaction. The type of crosslinking agent is not particularly limited, for example, it can be selected from existing known crosslinking agents according to the composition of the adhesive composition and in the manner in which the crosslinking agent plays an appropriate crosslinking function in the adhesive layer. As usable crosslinking agents, isocyanate crosslinking agents, epoxy crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, carbodiimide crosslinking agents, melamine crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, hydrazine crosslinking agents, amine crosslinking agents, etc. can be cited. They can be used alone or in combination of more than two. In some preferred embodiments, as a crosslinking agent, at least an isocyanate crosslinking agent is used. Isocyanate crosslinking agents and other crosslinking agents (for example, epoxy crosslinking agents) can be used in combination.

[0175] As the isocyanate crosslinking agent, a polyfunctional isocyanate compound having two or more functions can be used. Examples include aromatic isocyanates such as toluene diisocyanate, xylene diisocyanate, polymethylene polyphenyl diisocyanate, tris(p-isocyanatophenyl)phosphothioate, and diphenylmethane diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; aliphatic isocyanates such as 1,6-hexamethylene diisocyanate; and the like. Commercially available products include isocyanate adducts such as trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by Tosoh Corporation, trade name "Coronate L"), trimethylolpropane / 1,6-hexamethylene diisocyanate trimer adduct (manufactured by Tosoh Corporation, trade name "Coronate HL"), and isocyanurate of 1,6-hexamethylene diisocyanate (manufactured by Tosoh Corporation, trade name "Coronate HX").

[0176] As the epoxy crosslinking agent, an epoxy crosslinking agent having two or more epoxy groups in one molecule can be used without particular limitation. An epoxy crosslinking agent having 3 to 5 epoxy groups in one molecule is preferred. Specific examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl meta-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polyglycerol polyglycidyl ether, and the like. Commercially available products of epoxy crosslinking agents include trade names "TETRAD-X" and "TETRAD-C" manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "EPICLON CR-5L" manufactured by DIC Corporation, trade name "Denacol EX-512" manufactured by Nagase ChemteX Corporation, and trade name "TEPIC-G" manufactured by Nissan Chemical Industries, Ltd.

[0177] As the oxazoline crosslinking agent, any oxazoline crosslinking agent having one or more oxazoline groups in one molecule can be used without particular limitation.

[0178] Examples of the aziridine crosslinking agent include trimethylolpropane tris[3-(1-aziridinyl)propionate] and trimethylolpropane tris[3-(1-(2-methyl)aziridinylpropionate)].

[0179] As the carbodiimide-based crosslinking agent, a low molecular weight compound or a high molecular weight compound having two or more carbodiimide groups can be used.

[0180] Metal chelate crosslinking agents can typically be substances having a structure in which a polyvalent metal is covalently bonded or coordinately bonded to an organic compound. As the above-mentioned polyvalent metal atoms, Al, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Ba, Mo, La, Sn, Ti, etc. can be cited. Among them, Al, Zr, and Ti are preferred. In addition, as organic compounds, alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, ketone compounds, etc. can be cited. Metal chelate crosslinking agents can typically be compounds having a structure in which an oxygen atom in the organic compound is bonded (covalently bonded or coordinately bonded) to the above-mentioned polyvalent metal.

[0181] In some ways, as a crosslinking agent, peroxide can be used. As peroxide, di(2-ethylhexyl) peroxydicarbonate, di(4-tert-butylcyclohexyl) peroxydicarbonate, di-sec-butyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutyl peroxyisobutyrate, dibenzoyl peroxide, etc. can be cited. Among these, as a peroxide with particularly excellent crosslinking reaction efficiency, di(4-tert-butylcyclohexyl) peroxydicarbonate, dilauroyl peroxide, dibenzoyl peroxide, etc. can be cited. It should be noted that, when using peroxide as the above-mentioned polymerization initiator, the peroxide remaining without being used for polymerization reaction can also be used for crosslinking reaction. In this case, the residual amount of peroxide is quantitatively measured, and when the ratio of peroxide does not meet the prescribed amount, peroxide is added as required to make it a prescribed amount. The quantitative determination of peroxide can be carried out by the method described in Japanese Patent No. 4971517.

[0182] The amount of cross-linking agent used (when using two or more cross-linking agents, it is their total amount) is not particularly limited and can be appropriately set in a manner that can obtain the desired effect of use. From the viewpoint of the closeness to the adherend and the bonding reliability during the processing of the wafer (typically, semiconductor wafer), the amount of the cross-linking agent used relative to 100 parts by weight of the base polymer (e.g., acrylic polymer) is usually preferably less than about 15 parts by weight, preferably less than about 12 parts by weight, more preferably less than about 10 parts by weight, can be less than 7.0 parts by weight, can be less than 5.0 parts by weight, can be less than 4.0 parts by weight, can be less than 3.0 parts by weight, can be less than 2.0 parts by weight, can be less than 1.0 parts by weight, can be less than 0.5 parts by weight.

[0183] In addition, for example, for an adhesive sheet having an adhesive surface composed of an active energy ray-curable adhesive layer, from the perspective of exerting appropriate cohesiveness before curing treatment based on active energy rays, the amount of crosslinking agent used relative to 100 parts by weight of the base polymer (e.g., acrylic polymer) is usually suitable for about 0.005 parts by weight or more, preferably about 0.01 parts by weight or more, can be about 0.05 parts by weight or more, can be about 0.1 parts by weight or more, can be about 0.2 parts by weight or more. In some embodiments, the amount of crosslinking agent used relative to 100 parts by weight of the base polymer is preferably greater than 0.3 parts by weight, more preferably greater than 0.5 parts by weight, can be greater than 1.0 parts by weight, can be greater than 1.5 parts by weight, can be greater than 2.0 parts by weight, can be greater than 3.0 parts by weight, and can be greater than 4.0 parts by weight. For an adhesive sheet that can be used by water stripping after curing treatment based on active energy rays, if the amount of cross-linking agent used is increased, the strain caused by curing shrinkage will be easily maintained until the supply of aqueous stripping liquid, and the effect of light stripping brought about by the application of the water stripping method can be better exerted.

[0184] In the method of using an isocyanate crosslinking agent as a crosslinking agent, from the viewpoint of exerting appropriate cohesiveness before curing treatment, the amount of the isocyanate crosslinking agent used relative to 100 parts by weight of the base polymer is usually preferably about 0.005 parts by weight or more, preferably about 0.01 parts by weight or more, can be about 0.05 parts by weight or more, can be about 0.1 parts by weight or more, can be about 0.2 parts by weight or more, can be greater than 0.3 parts by weight, can be greater than 0.5 parts by weight, can be greater than 1.0 parts by weight, can be greater than 1.5 parts by weight, can be greater than 2.0 parts by weight, can be greater than 3.0 parts by weight, can be greater than 4.0 parts by weight. For an adhesive sheet that can be used by water stripping after curing treatment based on active energy rays, by increasing the amount of the isocyanate crosslinking agent used, the effect of light stripping brought about by the application of the water stripping method can be better exerted.

[0185] In addition, the amount of isocyanate cross-linking agent used relative to 100 parts by weight of the base polymer is generally preferably about 15 parts by weight or less. From the viewpoint of adhesion to the adherend during wafer (typically, semiconductor wafer) processing, bonding reliability, etc., it is preferably about 12 parts by weight or less, and more preferably about 10 parts by weight or less. It can be less than 7.0 parts by weight, less than 5.0 parts by weight, less than 4.0 parts by weight, less than 3.0 parts by weight, less than 2.0 parts by weight, less than 1.0 parts by weight, and less than 0.5 parts by weight.

[0186] In order to make the cross-linking reaction more effectively, a cross-linking catalyst can be used. As a cross-linking catalyst, metal cross-linking catalysts such as tetra-n-butyl titanate, tetraisopropyl titanate, ferric acetylacetonate, butyl tin oxide, dioctyltin dilaurate, etc. can be exemplified. Among them, tin-based cross-linking catalysts such as dioctyltin dilaurate are preferred. The amount of the cross-linking catalyst used is not particularly limited. The amount of the cross-linking catalyst used relative to 100 parts by weight of the base polymer can be, for example, about 0.0001 parts by weight or more and 1 part by weight or less, can be 0.001 parts by weight or more and 0.1 parts by weight or less, can be 0.005 parts by weight or more and 0.5 parts by weight or less.

[0187] (Multifunctional monomer)

[0188] In the adhesive layer, a multifunctional monomer can be used as needed. For the multifunctional monomer, it can be used instead of the above-mentioned cross-linking agent, or used in combination with the cross-linking agent, and can play a role for the purpose of adjusting cohesion. As a multifunctional monomer, a compound having two or more carbon-carbon double bonds (for example, ethylenically unsaturated groups such as (meth) acryloyl) can be used. The multifunctional monomer can be contained in the adhesive layer in an unreacted form, and can also be contained in the adhesive layer in a form after reaction (after cross-linking). The adhesive layer containing unreacted multifunctional monomers can be the following active energy ray-curable adhesive layer: by irradiating the adhesive layer with active energy rays such as ultraviolet rays, the above-mentioned multifunctional monomers are reacted, so that a cross-linked structure can be formed.

[0189] Examples of the polyfunctional monomer include ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butanediol (meth)acrylate, and hexanediol di(meth)acrylate. Among them, trimethylolpropane tri(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and dipentaerythritol hexa(meth)acrylate can be preferably used. The polyfunctional monomer can be used alone or in combination of two or more.

[0190] The appropriate amount of use when using a multifunctional monomer varies according to its molecular weight, number of functional groups, etc., and is usually suitable in the range of about 0.01 to 3.0 parts by weight relative to 100 parts by weight of a base polymer (e.g., an acrylic polymer). In some embodiments, the amount of a multifunctional monomer used relative to 100 parts by weight of a base polymer can be, for example, 0.02 parts by weight or more, 0.1 parts by weight or more, 0.5 parts by weight or more, 1.0 parts by weight or more, or 2.0 parts by weight or more. By increasing the amount of a multifunctional monomer used, there is a tendency to obtain a higher cohesive force. On the other hand, from the perspective of avoiding the decrease in adhesion during wafer processing and the decrease in the storage stability of the adhesive sheet due to excessive cohesive force improvement, the amount of a multifunctional monomer used relative to 100 parts by weight of a base polymer can be, for example, 10 parts by weight or less, 5.0 parts by weight or less, or 3.0 parts by weight or less. Alternatively, a multifunctional monomer may not be used. For example, the adhesive layer containing a polymer having a structure (carbon-carbon double bond, benzophenone structure, etc.) that causes a crosslinking reaction by irradiation with active energy rays can be an adhesive layer that substantially does not contain unreacted multifunctional monomers, or an adhesive layer formed by an adhesive composition that substantially does not contain multifunctional monomers. Here, the so-called adhesive composition substantially does not contain multifunctional monomers, which means that the amount of multifunctional monomers relative to 100 parts by weight of the base polymer is less than 0.05 parts by weight (for example, less than 0.01 parts by weight).

[0191] (Other optional ingredients)

[0192] In the adhesive layer (which can be an active energy ray-curable adhesive layer.), as required, various additives conventional in the field of adhesives such as tackifier resins (for example, rosin-based, petroleum-based, terpene-based, phenol-based, ketone-based, etc.), viscosity modifiers (for example, tackifiers), leveling agents, plasticizers, fillers, pigments, dyes, stabilizers, preservatives, antioxidants, anti-aging agents, etc. can be included as other optional components. Regarding such various additives, conventional methods can be used to use existing known additives, and detailed description is omitted because it is not particularly a material that imparts characteristics to the present invention.

[0193] From the perspective of achieving good balance between the adhesion to the adherend during wafer processing and the peelability when removed from the adherend (e.g., peelability based on water peeling), in some embodiments, the content of the tackifier resin in the adhesive layer is, for example, less than 5 parts by weight, and can be less than 3 parts by weight, can be less than 1 part by weight, can be less than 0.5 parts by weight, can be less than 0.1 parts by weight, relative to 100 parts by weight of the base polymer. It can be an adhesive layer that does not substantially contain a tackifier resin (e.g., the content of the adhesive layer relative to 100 parts by weight of the base polymer is 0 to 0.05 parts by weight). When the content of the tackifier resin is limited as described above, it can also be advantageous, for example, from the perspective of improving the curability of the active energy ray-curable adhesive layer.

[0194] In some preferred embodiments, the adhesive layer may be a composition in which the content of the polymer (typically, the base polymer) accounts for more than about 80% by weight of the total weight of the adhesive layer. Thus, it is desirable to achieve an effect of reducing the peeling force by applying water peeling (light peeling effect). From such a viewpoint, the content of the polymer is preferably more than about 85% by weight of the total weight of the adhesive layer, more preferably more than about 90% by weight, more preferably more than about 92% by weight, more preferably more than about 95% by weight.

[0195] (Active Energy Ray-Curing Adhesive Layer)

[0196] In some ways, the adhesive layer constituting the adhesive surface is preferably an adhesive layer (active energy ray curing adhesive layer) consisting of an active energy ray curing adhesive. For the adhesive sheet having the adhesive layer, after being attached to the adherend, the active energy ray is irradiated to cure the active energy ray curing adhesive layer, and then, an aqueous stripping liquid such as water is supplied to the peeling front of the peeling peeled off from the adherend, and peeling (water stripping) is performed, thereby, the peeling force peeled off from the above-mentioned adherend can be particularly effectively reduced. As its reason, although not particularly restrictive explanation, it can be considered as follows: when irradiating the active energy ray to the active energy ray curing adhesive layer in the state of being attached to the adherend, due to the rapid curing shrinkage of the adhesive layer, a tiny floating or strain from the adherend is accumulated in the adhesive layer, and if an aqueous stripping liquid is supplied in this state, the penetration of the aqueous stripping liquid to the interface of the adhesive layer and the adherend is carried out quickly, and the peeling force is effectively reduced. For an adhesive sheet constructed in such a manner that the adhesive layer is cured by irradiation with active energy rays, thereby reducing the peeling force, after being irradiated with active energy rays, the adhesive sheet is peeled off by a water peeling method. As a result, a particularly significant light peeling effect can be exerted through the synergistic effect of the reduction in peeling force brought about by the curing of the adhesive layer and the reduction in water peeling force brought about by the above-mentioned rapid curing shrinkage.

[0197] In some embodiments, the active energy ray-curable adhesive layer is preferably configured in such a manner that the adhesive layer is cured by irradiating active energy rays after being attached to an adherend, thereby reducing the peeling force from the adherend compared to before irradiation. For an adhesive sheet having such an active energy ray-curable adhesive layer, the bonding reliability with respect to the adherend is good before irradiation with active energy rays, and after irradiation with active energy rays, the peeling force can be significantly reduced by peeling with an aqueous peeling liquid.

[0198] As a preferred example of an active energy ray-curable adhesive layer, an example in which a carbon-carbon double bond is included in the adhesive layer to exert curability can be cited. The carbon-carbon double bond does not react with moisture, acidity, etc. in the air in a common storage environment that can be used industrially, and the chemical properties are stable. On the other hand, when free radicals are generated by irradiating active energy rays, a reaction (such as a polymerization reaction, a cross-linking reaction) is carried out to cure. From the viewpoint of ease of handling, light (such as ultraviolet rays) can be cited as a preferred active energy ray.

[0199] In the adhesive layer that exerts curability by including carbon-carbon double bonds, the existence form of the carbon-carbon double bonds in the adhesive layer is not particularly limited. The above-mentioned carbon-carbon double bonds can be included in the adhesive layer in the form of polymers (such as base polymers) with carbon-carbon double bonds, monomers (such as unreacted multifunctional monomers such as the above-mentioned) with carbon-carbon double bonds. They can be used alone or in combination of two or more.

[0200] The form of the carbon-carbon double bond contained in the polymer and the form of the carbon-carbon double bond contained in the monomer are not particularly limited. For example, the carbon-carbon double bond can exist in the polymer or monomer in the form of an ethylenically unsaturated group. Examples of ethylenically unsaturated groups include (meth)acryloyl, vinyl, allyl, methallyl, etc. From the viewpoint of reactivity, (meth)acryloyl is preferred.

[0201] (Polymers with carbon-carbon double bonds)

[0202] In some embodiments, the active energy ray-curable adhesive layer preferably includes a polymer having a carbon-carbon double bond. Hereinafter, the polymer having a carbon-carbon double bond is also referred to as "polymer (PD)". For example, a polymer (PD) having a carbon-carbon double bond in the form of an ethylenically unsaturated group is preferably used. In some preferred embodiments, the polymer (PD) can be included in the active energy ray-curable adhesive layer as a base polymer of the adhesive layer. In some other embodiments, the polymer (PD) can be included in the active energy ray-curable adhesive layer as a secondary component used in addition to the base polymer that does not contain a carbon-carbon double bond. It can be an active energy ray-curable adhesive layer comprising a polymer (PD) as a base polymer and further comprising a monomer having a carbon-carbon double bond (e.g., an unreacted multifunctional monomer) as a secondary component.

[0203] The form of the carbon-carbon double bond possessed by the polymer (PD) is not particularly limited. The polymer (PD) may be a polymer having a carbon-carbon double bond in a side chain, or a polymer having a carbon-carbon double bond in a main chain. Here, the so-called having a carbon-carbon double bond in the main chain includes the case where a carbon-carbon double bond exists in the main chain skeleton of the polymer (PD) and the case where a carbon-carbon double bond exists at the end of the main chain. From the viewpoint of the reactivity of the carbon-carbon double bond, a polymer (PD) having a carbon-carbon double bond in a side chain may be preferably used. The method of including a carbon-carbon double bond in a polymer (PD) is not particularly limited, and an appropriate method may be selected from methods known to those skilled in the art.

[0204] There are no particular restrictions on the polymer (PD), and an appropriate polymer can be selected for use in consideration of the characteristics of the adhesive layer, etc. As the polymer (PD), a polymer (secondary polymer) obtained by introducing carbon-carbon double bonds into a polymer (primary polymer) that does not contain carbon-carbon double bonds or has a carbon-carbon double bond content less than the target by chemical modification or the like can be preferably used.

[0205] As a specific example of a method for introducing a carbon-carbon double bond into a primary polymer, the following method can be cited: a primary polymer obtained by copolymerizing a monomer having a functional group (functional group A) is prepared, and the primary polymer is reacted with a compound having a functional group (functional group B) and a carbon-carbon double bond in one molecule (hereinafter also referred to as "unsaturated compound containing functional group B") in such a manner that the carbon-carbon double bond does not disappear. The reaction between functional group A and functional group B is preferably a reaction that is not accompanied by the generation of free radicals, such as a condensation reaction or an addition reaction.

[0206] As an example of the combination of functional group A and functional group B, a combination of carboxyl and epoxy, a combination of carboxyl and aziridine, a combination of hydroxyl and isocyanate, etc. can be cited. Among them, from the viewpoint of reaction traceability, a combination of hydroxyl and isocyanate is preferred. In addition, the combination of the above-mentioned functional groups A and B can be any combination that can obtain a polymer with a carbon-carbon double bond, and the functional group of one side in the above-mentioned combination can be functional group A, and the other side can be functional group B, or the functional group of the above-mentioned one side can be functional group B, and the other side can be functional group A. For example, if the combination of hydroxyl and isocyanate is used for explanation, functional group A can be hydroxyl (in this case, functional group B becomes isocyanate), or it can be isocyanate (in this case, functional group B becomes hydroxyl). Among them, it is preferred that a primary polymer has a hydroxyl group and the above-mentioned compound has a combination of isocyanate. This combination is particularly preferred when the primary polymer is an acrylic polymer.

[0207] In addition, as a preferred example of a method for obtaining a polymer having a carbon-carbon double bond, the following method can also be cited: using a vinyl alcohol polymer (typically, polyvinyl alcohol) as the above-mentioned primary polymer, the vinyl alcohol polymer (typically, a vinyl alcohol polymer not containing a carbon-carbon double bond) is reacted with a vinyl halide such as vinyl bromide, an allyl halide such as allyl bromide. In this method, the above-mentioned reaction can be carried out under appropriate alkaline conditions, and through this reaction, a vinyl alcohol polymer containing a vinyl group in a side chain can be obtained. In addition, for example, a method for preparing a polymer having a carbon-carbon double bond using a microorganism that produces a polymer as disclosed in Japanese Patent Gazette No. 4502363 can be adopted. Various conditions such as the microbial species and microbial culture conditions in this method can be set by using the conditions described in the above-mentioned patent gazette, or by appropriately changing them within the scope of the technical common sense of those skilled in the art.

[0208] For the molar amount (M A ) and the molar mass of functional group B (M B ) molar ratio (M A / M B ), from the viewpoint of the reactivity of the two, it is usually preferably 0.2 or more, can be 0.5 or more, can be 0.7 or more, can be 1.0 or more. In some embodiments, the molar ratio (M A / M B ) may be greater than 1.0, greater than 1.5, or greater than 2.0. For example, when the functional group A is used in other reactions (crosslinking reaction with a crosslinking agent, etc.), it is preferred to make the molar ratio (M A / M B ) is greater than 1.0. In addition, the molar ratio (M A / M B) may be, for example, 20 or less. In some embodiments, from the perspective of achieving both good balance between adhesion to an adherend before light irradiation and peelability from the adherend after light irradiation (for example, peelability by water peeling), the molar ratio (M A / M B ) is preferably less than 10, can be less than 5.0, can be less than 2.5, can be less than 1.8, and can be less than 1.5.

[0209] The amount of the compound having a functional group B and a carbon-carbon double bond (hereinafter also referred to as "unsaturated compound containing a functional group B") used is such that the above molar ratio (M A / M B ), for example, it can be 1.0 parts by weight or more, 3.0 parts by weight or more, 5.0 parts by weight or more, or 7.0 parts by weight or more, relative to 100 parts by weight of the primary polymer having the functional group A. From the viewpoint of achieving both the adhesion before light irradiation and the peelability after light irradiation (for example, peelability based on water peeling) at a higher level, in some embodiments, the amount of the unsaturated compound containing the functional group B relative to 100 parts by weight of the above-mentioned primary polymer is preferably 9.0 parts by weight or more, more preferably 10 parts by weight or more, 12 parts by weight or more, 14 parts by weight or more, or 16 parts by weight or more. In addition, the amount of the unsaturated compound containing the functional group B relative to 100 parts by weight of the above-mentioned primary polymer can be, for example, less than 40 parts by weight, usually, preferably less than 35 parts by weight, preferably less than 30 parts by weight, less than 25 parts by weight, or less than 20 parts by weight. In some embodiments, the amount of the unsaturated compound containing the functional group B used relative to 100 parts by weight of the primary polymer may be less than 18 parts by weight, less than 16 parts by weight, less than 13 parts by weight, less than 10 parts by weight, or less than 7 parts by weight.

[0210] As a preferred example of a polymer having a carbon-carbon double bond, an acrylic polymer having a (meth)acryloyl group introduced into a side chain can be cited. Such an acrylic polymer can be obtained, for example, by reacting an acrylic primary polymer having a hydroxyl group (functional group A) introduced by copolymerization with a compound having a carbon-carbon double bond and an isocyanate group (functional group B) so that the carbon-carbon double bond does not disappear.

[0211] In addition, the polymer having a carbon-carbon double bond may be, for example, a diene polymer (typically, a conjugated diene polymer). A diene polymer (typically, a conjugated diene polymer) is typically a polymer obtained by polymerizing or copolymerizing a diene (typically, a conjugated diene). Examples of the diene polymer (typically, a conjugated diene polymer) include butadiene polymers such as polybutadiene and styrene butadiene copolymers; isoprene polymers such as polyisoprene and styrene isoprene copolymers; chloroprene polymers such as polychloroprene; and the like.

[0212] As another example of the active energy ray-curable adhesive layer, there can be mentioned an adhesive layer containing a polymer having a structure other than a carbon-carbon double bond that causes a crosslinking reaction by irradiation with active energy rays. For example, an adhesive containing a polymer having a benzophenone structure in a side chain can exhibit active energy ray curability by photocrosslinking using the benzophenone structure. As the polymer having a benzophenone structure in a side chain, an acrylic polymer having a benzophenone structure in a side chain can be preferably used.

[0213] (Photoinitiator)

[0214] When ultraviolet rays are used as the active energy rays for curing the active energy ray-curable pressure-sensitive adhesive layer, it is preferred that the pressure-sensitive adhesive layer contain a photoinitiator from the viewpoint of promoting the reaction or improving the efficiency of light energy utilization.

[0215] Examples of the photoinitiator include benzoin ether photoinitiators, acetophenone photoinitiators, α-hydroxyketone photoinitiators, aromatic sulfonyl chloride photoinitiators, photoactive oxime photoinitiators, benzoin photoinitiators, benzyl photoinitiators, benzophenone photoinitiators, ketal photoinitiators, thioxanthone photoinitiators, α-aminoketone photoinitiators, acylphosphine oxide photoinitiators, etc. The photoinitiator may be used alone or in combination of two or more.

[0216] Examples of benzoin ether-based photoinitiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of acetophenone-based photoinitiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxy-cyclohexyl-phenyl ketone, 4-phenoxydichloroacetophenone, and 4-tert-butyl-dichloroacetophenone. Examples of α-hydroxyketone-based photoinitiators include 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, and the like. Examples of aromatic sulfonyl chloride-based photoinitiators include 2-naphthalenesulfonyl chloride, and the like. As photoactive oxime photoinitiators, for example, 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime, etc. can be mentioned. As benzoin-based photoinitiators, for example, benzoin, etc. can be mentioned. As benzyl-based photoinitiators, for example, benzyl, etc. can be mentioned. As benzophenone-based photoinitiators, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone, etc. can be mentioned. As ketal-based photoinitiators, for example, benzyldimethylketal, etc. can be mentioned. Examples of thioxanthone-based photoinitiators include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone. Examples of α-aminoketone-based photoinitiators include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone. Examples of acylphosphine oxide-based photoinitiators include 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.

[0217] As the photoinitiator, commercially available products can be used, such as trade names "Omnirad 651", "Omnirad 184", "Omnirad 2959", "Omnirad 907", "Omnirad 369", "Omnirad 1173", "Omnirad TPO" and the like manufactured by IGM Regins.

[0218] In some embodiments, as a photoinitiator, a photoinitiator that is not easily decomposed or generates free radicals by heating can be used. For example, as a photoinitiator, a heat-resistant photoinitiator with a 10% weight reduction temperature of 200°C or above can be used. By using such a heat-resistant photoinitiator, even if it is exposed to high temperature before curing, the following effect can be exerted: it is not easy to damage the peeling force reduction effect brought about by the curing treatment based on active energy rays. It should be noted that the so-called 10% weight reduction temperature refers to the ambient temperature at the time point when the weight of the photoinitiator is reduced by 10% by weight relative to the weight before heating (that is, the weight of the photoinitiator becomes 90% by weight relative to the weight before heating) when the ambient temperature is raised from 23°C to 300°C at a heating rate of 2°C / min when the photoinitiator is placed in a nitrogen atmosphere. The 10% weight reduction temperature of the photoinitiator is more preferably above 210°C, and more preferably above 220°C. Examples of photoinitiators having a 10 wt % reduction temperature within such a range include "Omnirad 369", "Omnirad 127", "Omnirad 379", and "Omnirad 819" manufactured by IGM Regins; "Irgacure OXE02" manufactured by BASF Japan; "Esacur one" and "Esacur 1001m" manufactured by Lamberti; and "ADEKA OPTOMER N-1414", "ADEKA OPTOMER N-1606", and "ADEKA OPTOMER N-1717" manufactured by Asahi Denka Industries.

[0219] The adhesive layer containing a photoinitiator can be formed using an adhesive composition containing the photoinitiator. There is no particular limitation on the method of making the adhesive composition contain a photoinitiator. For example, a photoinitiator is added to the adhesive composition, typically a liquid containing a polymer (polymer that has completed polymerization), and mixed. In this method, the photoinitiator can be added to the composition together with other added components (such as a cross-linking agent, etc.). As another method, a method of adding a polymerization initiator that can function as a photoinitiator during polymer polymerization can be cited. In this method, the polymerization initiator can be added in a manner that a specified amount remains after polymerization. The residual amount of the polymerization initiator (the amount of the photoinitiator present) can be adjusted not only by the amount of the polymerization initiator added, but also by the polymer polymerization conditions, the drying conditions when the adhesive layer is formed, the curing conditions, etc.

[0220] When the adhesive layer contains a photoinitiator, the content of the photoinitiator in the adhesive layer is not particularly limited and can be set in a manner that can appropriately exert the desired effect. In some embodiments, the content of the photoinitiator can be, for example, about 0.05 parts by weight or more, preferably about 0.1 parts by weight or more, and more preferably about 0.5 parts by weight or more, relative to 100 parts by weight of the base polymer of the adhesive layer. By increasing the content of the photoinitiator, the active energy ray curing property of the adhesive layer is improved. In some embodiments, the content of the photoinitiator relative to 100 parts by weight of the base polymer can be, for example, about 1.0 parts by weight or more, about 2.0 parts by weight or more, or about 2.5 parts by weight or more. In addition, the content of the photoinitiator relative to 100 parts by weight of the base polymer can be, for example, about 20 parts by weight or less, usually, preferably about 10 parts by weight or less, preferably about 8 parts by weight or less, about 6 parts by weight or less, or about 4 parts by weight or less. It is preferred that the content of the photoinitiator is not too high from the viewpoint of the storage stability of the PSA layer and the PSA sheet (for example, the performance of suppressing a change in performance due to storage of the PSA sheet before use).

[0221] <Formation of Adhesive Layer>

[0222] The adhesive layer (e.g., active energy ray-curable adhesive layer) of the adhesive sheet disclosed in this specification can be an adhesive layer formed by an adhesive composition containing a base polymer (e.g., an acrylic polymer) and other optional components as needed. The above-mentioned adhesive composition can be in the following various forms: a solvent-type adhesive composition in the form of containing an adhesive (adhesive component) in an organic solvent; an active energy ray-curable adhesive composition prepared in a manner of curing by active energy rays such as ultraviolet rays and radiation to form an adhesive; a water-dispersible adhesive composition in the form of an adhesive dispersed in water; a hot melt adhesive composition that is applied in a heated molten state and forms an adhesive when cooled to near room temperature; and the like. It should be noted that the above-mentioned active energy ray-curable adhesive composition is typically a liquid composition that shows fluidity to the extent that it can be applied at room temperature (approximately 0°C to 40°C, for example, about 25°C) and is cured by irradiation with active energy rays to form an adhesive (viscoelastic body).

[0223] The adhesive sheet of some embodiments may have an adhesive layer formed using a solvent-based adhesive composition or an active energy ray-curable adhesive composition. As the adhesive composition for forming the active energy ray-curable adhesive layer, a solvent-based adhesive composition may be preferably used from the viewpoint of ease of control of the active energy ray curability, etc.

[0224] The adhesive layer of the adhesive sheet disclosed in this specification can be formed by applying (e.g., coating) the adhesive composition to a suitable surface, and then appropriately implementing curing treatment (drying, crosslinking, polymerization, etc.). In the case of carrying out two or more curing treatments, they can be carried out simultaneously or through multiple steps. The adhesive layer of the multilayer structure of more than two layers can be made by laminating the preformed adhesive layer. Alternatively, an adhesive composition can be applied on the preformed first adhesive layer, and the adhesive composition is cured to form a second adhesive layer.

[0225] The adhesive composition can be applied by using a conventional coating machine such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a rod coater, a knife coater, a spray coater, etc. For an adhesive sheet having a support body, as a method for providing an adhesive layer on the support body, a direct method of directly applying the adhesive composition to the support body to form the adhesive layer can be used, and a transfer method of transferring the adhesive layer formed on the release surface to the support body can also be used.

[0226] In the adhesive sheet disclosed in this specification, the thickness of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose. Usually, the thickness of the adhesive layer is about 5 to 200 μm, and from the viewpoint of adhesion, it is preferably about 10 μm or more (for example, 15 μm or more), and can be 25 μm or more. In addition, it is preferably 150 μm or less, more preferably 100 μm or less, and further preferably 80 μm or less (for example, 60 μm or less, typically 40 μm or less), and can be 35 μm or less or less than 30 μm. In the case of a double-sided adhesive sheet having an adhesive layer on both sides of a substrate, the thickness of each adhesive layer can be the same or different.

[0227] <Additional adhesive layer>

[0228] In some ways of the adhesive sheet disclosed in this specification, the adhesive sheet can be a structure formed by stacking an additional adhesive layer on the back side (the side opposite to the adhesive surface) of the adhesive layer constituting the adhesive surface. The adhesive layer constituting the adhesive surface is preferably directly contacted and stacked with the additional adhesive layer. That is, preferably there is no diaphragm layer (for example, resin films such as polyester films) that completely separates two adhesive layers between the adhesive layer constituting the adhesive surface and the additional adhesive layer. The additional adhesive layer can be, for example, an adhesive layer consisting of one or more adhesives selected from various known adhesives such as acrylic adhesives, rubber adhesives (natural rubber system, synthetic rubber system, their mixed systems, etc.), polysiloxane adhesives, polyester adhesives, urethane adhesives, polyether adhesives, polyamide adhesives, fluorine adhesives, etc. Consider from the viewpoints such as transparency and weather resistance, in some ways, as the constituent material of the additional adhesive layer, acrylic adhesives can be preferably adopted. Other matters regarding the additional adhesive layer may be of the same configuration as the above-mentioned adhesive layer, or may be of an appropriate configuration according to the use and purpose based on known or customary techniques and technical common sense, and therefore, detailed descriptions thereof are omitted here.

[0229] <Base material>

[0230] In the adhesive sheet with substrate of single-sided adhesive type or double-sided adhesive type, as the substrate of supporting (lining) adhesive layer, various sheet substrates such as resin film, paper, cloth, rubber sheet, foam sheet, metal foil, their composite can be used. The above-mentioned substrate can be a monolayer, or a laminate of the same or different substrates. It should be noted that in this specification, the so-called monolayer refers to the layer formed by the same composition, including the layer of the form formed by the stacking of multiple layers formed by the same composition.

[0231] In a preferred embodiment, a substrate (resin film substrate) with a resin sheet as the main component can be used. As the resin constituting the substrate, for example, low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, ultra-low-density polyethylene, random copolymer polypropylene, block copolymer polypropylene, homopolymer polypropylene, polybutene, polymethylpentene, ethylene-vinyl acetate copolymer (EVA), ionomer, ethylene-(methyl) acrylic acid copolymer, ethylene-(methyl) acrylic acid ester (random, alternating) copolymer, ethylene-butene copolymer, ethylene-hexene copolymer and other polyolefin resins; polyurethane; polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate, and polybutylene terephthalate (PBT); polycarbonate; polyimide; polyetheretherketone; polyetherimide; polyamides such as aramid and wholly aromatic polyamide; polyphenylene sulfide; fluororesin; polyvinyl chloride; polyvinylidene chloride; cellulose resin; polysiloxane resin; and the like. The above resins can be used alone or in combination of two or more to form the entire or a part of the substrate (for example, any layer in a substrate with a laminated structure of two or more layers). In the case where the adhesive layer constituting the bonding surface is an active energy ray-curable adhesive layer, the substrate preferably has active energy ray transmittance. In some embodiments, a substrate having an ultraviolet transmittance of 40% to 100% (more preferably 60% to 100%) at a wavelength of 365nm can be preferably used. When a substrate with high transmittance is used, the adhesive layer can be easily cured.

[0232] If necessary, various additives such as fillers (inorganic fillers, organic fillers, etc.), anti-aging agents, antioxidants, ultraviolet absorbers, antistatic agents, lubricants, plasticizers, colorants (pigments, dyes, etc.) may be blended into the base material.

[0233] The substrate can be manufactured by any suitable method. For example, known methods such as calendering, casting, expansion extrusion, and T-die extrusion can be used. In addition, as required, stretching treatment can be performed to manufacture.

[0234] For the purpose of improving the adhesion with the adhesive layer and the retention of the adhesive layer, the adhesive layer side surface of the substrate may be subjected to physical treatments such as corona discharge treatment, plasma treatment, sand pad processing treatment, ozone exposure treatment, flame exposure treatment, high voltage electric shock exposure treatment, ionizing radiation treatment, etc.; chemical treatments such as acid treatment, alkali treatment, chromic acid treatment, etc.; known or customary surface treatments such as easy adhesion treatment based on a coating agent (primer). In addition, for the purpose of imparting antistatic ability, a conductive vapor deposition layer containing metals, alloys, their oxides, etc. may be provided on the substrate surface.

[0235] In some preferred embodiments, a primer layer may be provided on the adhesive layer side surface of the substrate. In other words, a primer layer may be configured between the substrate and the adhesive layer. As the primer layer forming material, there is no particular restriction, and one or more of urethane (polyisocyanate) resins, polyester resins, acrylic resins, polyamide resins, melamine resins, olefin resins, polystyrene resins, epoxy resins, phenolic resins, isocyanurate resins, polyvinyl acetate resins, etc. may be used. In the case where an adhesive layer of acrylic acid or the like is provided on a resin film substrate via a primer layer, a primer layer of polyester, urethane, or acrylic acid is preferred. In the case where an acrylic adhesive layer is provided on a polyester substrate such as a PET film via a primer layer, a polyester primer layer is particularly preferred. The thickness of the primer layer is not particularly limited, and may generally be in the range of about 0.1 μm to 10 μm (e.g., 0.1 μm to 3 μm, typically 0.1 μm to 1 μm). The undercoat layer can be formed using a known or commonly used coater such as a gravure roll coater or a reverse roll coater.

[0236] In the case where the adhesive sheet disclosed in this specification is a single-sided adhesive sheet having an adhesive layer provided on one side of a substrate, a release treatment agent (back side treatment agent) can be used to perform a release treatment on the non-adhesive layer forming side (back side) of the substrate. There are no particular restrictions on the back side treatment agent that can be used to form the back side treatment layer, and known or commonly used treatment agents such as polysiloxane-based back side treatment agents, fluorine-based back side treatment agents, and long-chain alkyl-based back side treatment agents can be used according to the purpose and application.

[0237] The thickness of the substrate is not particularly limited, and can be appropriately selected according to the purpose. Usually, it can be about 3μm to 800μm. From the viewpoints of the processability and operability of the adhesive sheet (for example, the workability during the attachment and peeling of the adherend), the thickness of the substrate is preferably more than 5μm, and is preferably more than 10μm. From the viewpoint of improving the protectiveness of the adherend in the wafer processing, it is preferably more than 20μm, more than 30μm, and more than 40μm. In some ways that pay more attention to protectiveness, the thickness of the substrate can be, for example, more than 55μm, more than 75μm or more than 90μm. In addition, from the viewpoints of reducing the load on the adherend when peeling from the adherend, the thickness of the substrate is usually suitable for less than 300μm, preferably less than 200μm, less than 150μm, less than 125μm, less than 80μm, and less than 60μm.

[0238] The total thickness of the adhesive sheet disclosed in this specification (which may include an adhesive layer and a substrate, but does not include a release liner) is not particularly limited, and is preferably in the range of about 10 μm to 1000 μm. Considering the adhesion and operability, the total thickness of the adhesive sheet is preferably in the range of about 15 μm to 300 μm, and more preferably in the range of about 20 μm to 200 μm. In addition, from the perspective of improving the protection of the adherend during wafer processing, it is advantageous for the total thickness of the adhesive sheet to be more than about 30 μm, preferably more than about 40 μm, and more preferably more than about 50 μm (for example, more than 60 μm). In some embodiments that place more emphasis on protection, the total thickness of the adhesive sheet may be greater than 65 μm, greater than 80 μm, or greater than 100 μm.

[0239] <Application>

[0240] The adhesive sheet disclosed in this specification can be used for the processing of various semiconductor wafers. The above-mentioned semiconductor wafer can be, for example, a compound semiconductor wafer such as a silicon wafer, a silicon carbide (SiC) wafer, a nitride semiconductor wafer (silicon nitride (SiN), gallium nitride (GaN), etc.), a gallium arsenide wafer, etc. For the adhesive sheet disclosed in this specification, in the process of manufacturing a semiconductor element (for example, a semiconductor chip) from such a semiconductor wafer, typically, in the method of being attached to the above-mentioned semiconductor wafer having a circuit formed by the previous process, it can be preferably used as an adhesive sheet for wafer processing for protecting and / or fixing the semiconductor wafer during the processing of the above-mentioned semiconductor wafer. After attaching the adhesive sheet disclosed in this specification, until the adhesive sheet is peeled off, the examples of processing that can be performed on the semiconductor wafer include back grinding and cutting, but are not limited to these. In addition, the adhesive sheet disclosed in this specification can also be used for non-semiconductor wafer processing such as glass and resin. It should be noted that in this specification, when the shape of a chip (typically a semiconductor chip) to be processed changes due to processing (for example, overall or partial thinning due to back grinding processing, a single chip obtained by cutting processing, etc.), the processed article is sometimes still referred to as a chip (typically a semiconductor chip).

[0241] The bonding of the adhesive sheet disclosed in this specification to a wafer (typically, a semiconductor wafer) can be performed using any appropriate method. The temperature when bonding the adhesive sheet can be around room temperature (e.g., 10°C to 35°C), or it can be a temperature higher than the room temperature range (e.g., higher than 35°C, preferably 60°C to 90°C). When bonding the adhesive sheet at a temperature higher than the room temperature range, it can be advantageous from the perspective of improving the adhesion of the adhesive sheet to the wafer. After bonding the adhesive sheet within the room temperature range, a heating and pressurizing treatment can be performed by applying a temperature higher than the room temperature range (e.g., 40°C to 90°C, preferably 40°C to 60°C) and a pressure higher than atmospheric pressure (e.g., 1.5 to 10 atm, preferably 3 to 7 atm). There is no particular restriction on the time for the above-mentioned heating and pressurizing treatment, and it can be set in a manner that can obtain a suitable treatment effect. In some embodiments, considering the balance between the stability of the treatment effect and the productivity, the time for the above-mentioned heating and pressurizing treatment can be set to 3 minutes to 1 hour (e.g., 5 minutes to 30 minutes).

[0242] In the case where the adhesive layer constituting the adhesive surface of the adhesive sheet disclosed in this specification is an active energy ray-curable adhesive layer, the adhesive sheet can preferably be used in a manner of irradiating with active energy rays and water-peeling after being attached to an adherend. The irradiation conditions of the active energy rays are not particularly limited and can be set in a manner that enables the curing of the active energy ray-curable adhesive layer to proceed appropriately. If it is a person skilled in the art, appropriate irradiation conditions can be set without excessive burden based on the technical common sense in this field, and therefore, detailed description is omitted. As an example, when ultraviolet rays are used as active energy rays, for the irradiation conditions of the ultraviolet rays, for example, the irradiation cumulative light amount can be made to be 50mJ / cm 2 ~5000mJ / cm 2 Range, about 50mJ / cm 2 ~2000mJ / cm 2 range or about 100mJ / cm 2 ~2000mJ / cm 2 In addition, the irradiation time can be in the range of about 1 second to 30 minutes.

[0243] <Semiconductor device manufacturing method>

[0244] An embodiment of a method for manufacturing a semiconductor element using the above-mentioned wafer processing adhesive sheet is described below. The semiconductor element manufacturing method of this embodiment includes the following steps: step (1), laminating the adhesive surface of the wafer processing adhesive sheet to the circuit forming surface side of a semiconductor wafer having a circuit forming surface; step (2), processing the semiconductor wafer to which the above-mentioned adhesive sheet is laminating from the side opposite to the adhesive sheet; and step (3), peeling the above-mentioned adhesive sheet from the processed semiconductor wafer.

[0245] Here, the above-mentioned process (3) is preferably carried out by supplying an aqueous stripping liquid to the stripping front of the above-mentioned adhesive sheet from the processed semiconductor wafer (adherend). Thus, the adhesive sheet can be lightly stripped, and the load given to the adherend (processed semiconductor wafer) during stripping can be reduced. Therefore, the above-mentioned adhesive sheet can be efficiently stripped while avoiding damage to the adherend. In some embodiments, the above-mentioned process (3) can be preferably implemented by the adhesive sheet stripping method described later.

[0246] It should be noted that as an aqueous stripping liquid in the technology disclosed in this specification (including adhesive sheets for wafer processing, adhesive compositions, semiconductor element manufacturing methods, adhesive sheet stripping methods, etc.), a liquid obtained by containing a small amount of additives as needed in water or a mixed solvent with water as the main component can be used. As solvents other than water constituting the above-mentioned mixed solvent, lower alcohols (such as ethanol), lower ketones (such as acetone), etc. that can be uniformly mixed with water can be used. As the above-mentioned additives, known surfactants, pH adjusters, etc. can be used. From the viewpoint of avoiding contamination of the adherend, in some methods, it is preferred to use an aqueous stripping liquid that does not substantially contain additives. From the viewpoint of environmental hygiene, it is particularly preferred to use water as an aqueous stripping liquid. As water, there is no particular restriction. Considering the purity required according to the application, ease of use, etc., for example, distilled water, ion exchange water, tap water, etc. can be used.

[0247] When the adhesive layer constituting the above-mentioned adhesive surface is an active energy ray-curable adhesive layer, before the adhesive sheet is peeled off, the process of curing the above-mentioned active energy ray-curable adhesive layer by irradiating active energy rays is performed. Typically, the peeling force of the adhesive sheet is reduced by the above-mentioned curing treatment. By water-peeling the adhesive sheet after the above-mentioned curing treatment, the load imparted to the adherend (processed semiconductor wafer) during peeling can be more effectively reduced. From the viewpoint of simultaneously realizing the bonding reliability relative to the adherend in the process (2) and the light peelability in the process (3), the above-mentioned curing treatment is preferably performed after the process (2).

[0248] In some embodiments, the above-mentioned step (2) may be a back grinding step. In this case, the adhesive sheet for wafer processing may be used as a back grinding tape. The back grinding step may be performed by any appropriate method. The back grinding step may be a step in which the semiconductor wafer to which the adhesive sheet is bonded is thinned until the thickness of the semiconductor wafer becomes, for example, less than 150 μm, less than 100 μm, less than 50 μm or less than 30 μm. As described above, in the method of thinning, the effect brought about by applying the technology disclosed in this specification can be appropriately exerted. It should be noted that the back grinding step may be performed in a manner in which the inner side of the annular convex portion becomes a concave portion (i.e., in a manner in which a TAIKO (registered trademark) wafer can be obtained). In this case, the thickness of the thinned semiconductor wafer refers to the thickness of the above-mentioned concave portion. In addition, although not particularly limited, the thickness of the semiconductor wafer before back grinding may be, for example, about 500 μm to 1000 μm.

[0249] The semiconductor element manufacturing method disclosed in this specification may further include any appropriate process. Examples of such arbitrary processes include etching process, photolithography process, ion implantation process, dicing process, die bonding process, wire bonding process, packaging process, etc., but are not limited to these. Each process listed above may be performed in the above-mentioned process (2), after the above-mentioned process (2) and before the above-mentioned process (3), or after the above-mentioned process (3).

[0250] <How to peel off the adhesive sheet>

[0251] According to the present specification, a method for peeling an adhesive sheet that has been attached to an adherend from the adherend can be provided. The method may include the following water peeling step, that is, at the peeling front of the adhesive sheet being peeled from the adherend, in a state where an aqueous peeling liquid exists at the interface between the adherend and the adhesive sheet, while following the movement of the peeling front and allowing the aqueous peeling liquid to enter the interface, the adhesive sheet is peeled from the adherend. The peeling front here refers to the position where the adhesive surface of the adhesive sheet begins to separate from the adherend when the adhesive sheet is peeled from the adherend. Through the above-mentioned water peeling step, the above-mentioned aqueous peeling liquid can be effectively used to peel the adhesive sheet from the adherend. The above-mentioned peeling method can be preferably implemented, for example, in a manner that any adhesive sheet disclosed in this specification is peeled from the adherend.

[0252] The adherend in the peeling method disclosed in this specification may be any of the semiconductor wafers exemplified above. The semiconductor wafer may be a semiconductor wafer having a circuit formed thereon. The peeling method disclosed in this specification may be preferably used as a method for peeling an adhesive sheet attached to the circuit-forming surface of a semiconductor wafer having a circuit formed thereon from the circuit-forming surface.

[0253] The adhesive sheet that can be peeled off from the adherend using the above-mentioned peeling method includes an adhesive layer constituting an adhesive surface, and the above-mentioned adhesive layer is composed of an adhesive. As the above-mentioned adhesive sheet, any adhesive sheet disclosed in this specification can be preferably used. Therefore, the above-mentioned peeling method is suitable for the peeling method of any adhesive sheet disclosed in this specification.

[0254] In some embodiments, the above-mentioned peeling method can be preferably implemented in a manner including the following steps: at one end of the outer edge of the adhesive sheet that has been attached to the adherend, the adhesive sheet is forcibly lifted from the adherend, thereby forming an initial peeling front; supplying an aqueous peeling liquid to the above-mentioned peeling front; and, while following the movement of the above-mentioned peeling front and entering the above-mentioned aqueous peeling liquid into the interface between the above-mentioned adhesive sheet and the above-mentioned adherend, the above-mentioned adhesive sheet is peeled from the above-mentioned adherend. The formation of the above-mentioned initial peeling front can be carried out, for example, by the following methods: inserting the front end of a tool such as a cutter or a needle into the interface between the adhesive sheet and the adherend; grabbing and lifting the above-mentioned adhesive sheet with a hook or a claw; attaching a strongly adhesive adhesive tape, a suction cup, etc. to the back of the adhesive sheet and lifting the end of the adhesive sheet; and so on. After the initial peeling front is formed by the above-mentioned operation, an aqueous peeling liquid is supplied to the peeling front to start water peeling, thereby enabling the supply of the aqueous peeling liquid to the above-mentioned peeling front to be carried out efficiently. In the above-mentioned peeling method and the pressure-sensitive adhesive sheet used in the peeling method, it is desirable to achieve both good water peelability after the start of peeling by forcibly forming an initial peeling front and high water resistance reliability without performing the operation.

[0255] In some embodiments, the above-mentioned stripping method can be preferably carried out in the following manner: after supplying an aqueous stripping liquid to the above-mentioned initial stripping front (i.e., after supplying an aqueous stripping liquid at the beginning of water stripping), the adhesive sheet is stripped without supplying a new aqueous stripping liquid. Alternatively, if the aqueous stripping liquid that follows the movement of the stripping front and enters the interface between the adhesive sheet and the adherend dries up or is insufficient midway during the water stripping, the aqueous stripping liquid can also be intermittently or continuously added after the start of the water stripping. For example, in the case where the length of the stripping front increases with the progress of the stripping (for example, the case where water stripping is performed radially from one end of the outer edge of the disc-shaped adherend along the circle), and the case where the aqueous stripping liquid is easily left on the surface of the adherend, it is preferred to adopt the method of adding the supply of aqueous stripping liquid after the start of water stripping. In addition, the position for supplying the aqueous stripping liquid can be one place or multiple places. In the case where the aqueous stripping liquid is added after the start of water stripping, the number of positions for supplying the aqueous stripping liquid after the start of water stripping can be increased or decreased.

[0256] Example

[0257] Hereinafter, some embodiments of the present invention will be described, but the present invention is not intended to be limited to the contents shown in the embodiments. It should be noted that in the following description, unless otherwise specified, "parts" and "%" are based on weight.

[0258] <Measurement of stickiness>

[0259] 1. Determination of the SSd0 of conventional peeling without irradiation

[0260] The non-UV-irradiated adhesive sheet as the test object was cut into a strip with a width of 10 mm to prepare a test piece. Under an environment of 23°C and 50% RH, the adhesive surface of the test piece was attached to the mirror surface of a 6-inch silicon wafer (manufactured by Shin-Etsu Chemical Co., Ltd., 6-inch N<100>-100) as the adherend using a hand roller and left at room temperature for 30 minutes to prepare an evaluation sample.

[0261] Then, in an environment of 23°C and 50% RH, a cutter was inserted into the interface between the test piece of the evaluation sample and the adherend, and one end of the test piece in the length direction was peeled off from the adherend. According to "10.4.1 Method 1: 180° peel adhesion relative to the test plate" of JIS Z0237:2009, specifically, at a test temperature of 23°C, a tensile testing machine (the device name is "tensile compression testing machine, VPA-3" manufactured by Kyowa Interface Science Co., Ltd.) was used to peel at a peeling speed of 300 mm / min and a peeling angle of 180 degrees until the peeling distance reached 100 mm, and the peeling force data was obtained every 0.25 mm of the peeling distance. Among the peeling forces obtained, the peeling force data when the peeling distance was 30 to 70 mm was used to calculate the stickiness of the adhesive sheet. The stickiness was measured three times, and their average value was taken as the normal peeling stickiness SSd0[10 -3 N / 10 mm]. The stickiness was measured by peeling the test piece attached to the adherend from bottom to top.

[0262] 2. Determination of non-irradiated water peeling viscosity SSw0

[0263] In the evaluation sample without UV irradiation, 20 μL of distilled water was supplied to the position where the test piece began to separate from the adherend (peeling interface) while the test piece was being peeled off from the adherend, and the viscosity after the distilled water supply was measured. The viscosity measurement was performed 3 times, and the average value was taken as the non-irradiated water peeling viscosity SSw0[10 -3 N / 10mm].

[0264] 3. Determination of conventional peeling slip SSd1 after irradiation

[0265] For the evaluation sample without UV irradiation prepared in the same manner as the measurement of the conventional peeling slip SSd0 without irradiation, the sample was irradiated with light from the substrate side of the adhesive sheet (the side opposite to the adhesive surface to be measured. Hereinafter, it is also referred to as the "back side") at an illumination of 60 mW / cm2 in an environment of 23°C and 50% RH under the following conditions using a UV irradiator manufactured by Nitto Seiki Co., Ltd., trade name "NELSYSTEM UM810" (high-pressure mercury lamp light source) at an illumination of 60 mW / cm2. 2 , cumulative light intensity is 500mJ / cm 2 UV rays under the conditions of.

[0266] Then, under an environment of 23°C and 50% RH, a cutter was inserted into the interface between the test piece of the evaluation sample after UV irradiation and the adherend, and one end of the test piece in the longitudinal direction was peeled off from the adherend. The stickiness was measured in the same manner as the measurement of the normal peeling stickiness SSd0 before irradiation. The measurement was performed three times, and the average value thereof was taken as the normal peeling stickiness SSd1 after irradiation [10 -3 N / 10mm].

[0267] 4. Determination of water peeling slip SSw1 after irradiation

[0268] The evaluation sample after UV irradiation was prepared in the same manner as the measurement of the conventional peeling viscosity SSd1 after irradiation. In the evaluation sample after UV irradiation, 20 μL of distilled water was supplied to the position where the test piece began to separate from the adherend (peeling interface) during the peeling of the test piece from the adherend, and the viscosity after the distilled water supply was measured. The viscosity measurement was performed 3 times, and the average value was taken as the water peeling viscosity SSw1 after irradiation [10 -3 N / 10mm].

[0269] <Measurement of peel force>

[0270] 1. Determination of conventional peeling force Fd0 without irradiation

[0271] The non-UV-irradiated adhesive sheet as the test object was cut into a strip with a width of 10 mm to prepare a test piece. Under an environment of 23°C and 50% RH, the adhesive surface of the test piece was attached to the mirror surface of a 6-inch silicon wafer (manufactured by Shin-Etsu Chemical Co., Ltd., 6-inch N<100>-100) as the adherend using a hand roller and left at room temperature for 30 minutes to prepare an evaluation sample.

[0272] Then, under the environment of 23°C and 50%RH, a cutter was inserted into the interface between the test piece of the evaluation sample and the adherend, and one end of the test piece in the length direction was peeled off from the adherend. According to "10.4.1 Method 1: 180° peeling adhesion relative to the test plate" of JIS Z0237:2009, specifically, the peeling force was measured at a test temperature of 23°C using a tensile tester (device name "DT9503-1000N" manufactured by Tansui Co., Ltd.) at a peeling speed of 300 mm / min and a peeling angle of 180 degrees. The measurement was performed three times, and their average value was taken as the normal peeling force Fd0 [N / 10mm] without irradiation. The peeling force was measured by peeling the test piece attached to the adherend from bottom to top.

[0273] 2. Determination of unirradiated water peeling force Fw0

[0274] In the evaluation sample without UV irradiation, 20 μL of distilled water was supplied to the position where the test piece began to separate from the adherend (peeling interface) while the test piece was being peeled off from the adherend, and the peeling force after the distilled water supply was measured. The peeling force was measured three times, and the average value was taken as the peeling force Fw0 [N / 10mm] without water irradiation.

[0275] 3. Determination of conventional peeling force Fd1 after irradiation

[0276] For the evaluation sample without UV irradiation prepared in the same manner as the measurement of the conventional peel force Fd0 without irradiation, a UV irradiator manufactured by Nitto Seiki Co., Ltd., trade name "NEL SYSTEM UM810" (high-pressure mercury lamp light source), was used at an illumination of 60 mW / cm2 from the substrate side of the adhesive sheet (the side opposite to the adhesive surface to be measured. Hereinafter, also referred to as the "back side") under an environment of 23°C and 50% RH. 2 , cumulative light intensity is 500mJ / cm 2 UV rays under the conditions of.

[0277] Then, under an environment of 23°C and 50% RH, a cutter was inserted into the interface between the test piece of the evaluation sample after UV irradiation and the adherend, and one end of the test piece in the longitudinal direction was peeled off from the adherend, and the peeling force was measured in the same manner as the measurement of the normal peeling force Fd0 before irradiation. The measurement was performed three times, and the average value thereof was taken as the normal peeling force Fd1 [N / 10mm] after irradiation.

[0278] 4. Determination of water peeling force Fw1 after irradiation

[0279] The evaluation sample after UV irradiation was prepared in the same manner as the measurement of the conventional peeling force Fd1 after irradiation. In the evaluation sample after UV irradiation, 20 μL of distilled water was supplied to the position where the test piece began to separate from the adherend (peeling interface) while the test piece was being peeled off from the adherend, and the peeling force after the distilled water supply was measured. The measurement was performed three times, and the average value thereof was taken as the water peeling force Fw1 [N / 10mm] after irradiation.

[0280] <Example 1>

[0281] (Preparation of Adhesive Composition)

[0282] Into a reaction vessel equipped with a Liebig condenser, a nitrogen inlet pipe, a thermometer and a stirring device, 100 parts of 2-ethylhexyl acrylate (2EHA) as monomer raw materials, 25.5 parts of acryloyl morpholine (ACMO) and 18.5 parts of 2-hydroxyethyl acrylate (HEA), and toluene as a polymerization solvent were added, and 0.3 parts of benzoyl peroxide (BPO) as a polymerization initiator were added, and solution polymerization was carried out under a nitrogen atmosphere, thereby obtaining a solution of polymer P1a. The weight average molecular weight (Mw) of polymer P1a is 900,000. The glass transition temperature (Tg) of polymer P1a based on the composition of the above monomer raw materials is -42.7°C.

[0283] After the solution of the above-mentioned polymer P1a was cooled to room temperature, 12.3 parts of 2-isocyanatoethyl methacrylate (manufactured by Showa Denko K.K., trade name "Karenz MOI") was added, and further 0.1 part of dibutyltin (IV) dilaurate (manufactured by Wako Pure Chemical Industries, Ltd.) was added, and the mixture was stirred at 50°C for 24 hours in an air atmosphere, thereby causing the above-mentioned polymer P1a and MOI to undergo an addition reaction to obtain a solution of polymer P1 having a carbon-carbon double bond.

[0284] To the solution of the polymer P1, 5 parts of an isocyanate crosslinking agent A1 (trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation, trade name "Coronate L", solid content concentration 75 wt%) were added based on the solid content, and 1 part of a photoinitiator (manufactured by IGM Regins, trade name "Omnirad 369") was further added and mixed to prepare an adhesive composition C1.

[0285] (Manufacturing of adhesive sheets)

[0286] The adhesive composition C1 was applied to the release surface of a release film R1 (MRF38 manufactured by Mitsubishi Plastics Co., Ltd.) having a thickness of 38 μm and a release surface treated with polysiloxane on one side of a polyethylene terephthalate (PET) film, and dried at 140° C. for 2 minutes to form an adhesive layer having a thickness of 20 μm. The adhesive layer was bonded to the easy-adhesion surface of an easy-adhesion treated PET film (50 μm thick) as a substrate, and then aged at 50° C. for 2 days to obtain the adhesive sheet involved in this example.

[0287] <Example 2>

[0288] To the solution of the polymer P1, 0.5 parts of a surfactant (polyoxyethylene sorbitan monolaurate, sorbitan fatty acid ester manufactured by Kao Corporation, trade name "Rheodol TW-L 120", ethylene oxide addition mole number 20, HLB 16.7) was further added relative to 100 parts of the polymer P1 in the solution. Except for the above aspects, an adhesive composition C2 was prepared in the same manner as the preparation of the adhesive composition C1. Except for using the adhesive composition C2, an adhesive sheet involved in this example was obtained in the same manner as the preparation of the adhesive sheet involved in Example 1.

[0289] It should be noted that the above-mentioned surfactant was used in the form of an ethyl acetate solution and added in the above-mentioned amount based on the solid content. Similarly, for adhesive compositions C4 and C7, the following amount of surfactant based on the solid content was added to the polymer solution in the form of an ethyl acetate solution.

[0290] <Example 3>

[0291] (Preparation of Adhesive Composition)

[0292] Into a reaction vessel equipped with a Liebig condenser, a nitrogen inlet pipe, a thermometer and a stirring device, 100 parts of n-butyl acrylate (BA), 78 parts of ethyl acrylate (EA) and 40 parts of 2-hydroxyethyl acrylate (HEA) as monomer raw materials, and toluene as a polymerization solvent, 0.3 parts of benzoyl peroxide (BPO) as a polymerization initiator were added, and solution polymerization was carried out under a nitrogen atmosphere to obtain a solution of polymer P3a. The weight average molecular weight (Mw) of polymer P3a is 500,000. The glass transition temperature (Tg) of polymer P3a based on the composition of the above monomer raw materials is -37.2°C.

[0293] After the solution of the above-mentioned polymer P3a was cooled to room temperature, 43.6 parts of 2-isocyanatoethyl methacrylate (produced by Showa Denko K.K., trade name "Karenz MOI") was added, and further 0.2 parts of dibutyltin (IV) dilaurate (produced by Wako Pure Chemical Industries, Ltd.) was added, and the mixture was stirred at 50°C for 24 hours in an air atmosphere, thereby causing the above-mentioned polymer P3a and MOI to undergo an addition reaction to obtain a solution of polymer P3 having a carbon-carbon double bond.

[0294] To the solution of the polymer P3, 5 parts of an isocyanate crosslinking agent A1 (trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation, trade name "Coronate L", solid content concentration of 75 wt%) were added based on the solid content, and 1 part of a photoinitiator (manufactured by IGM Regins, trade name "Omnirad 369") was added and mixed to prepare an adhesive composition C3. The adhesive sheet of this example was obtained in the same manner as the preparation of the adhesive sheet of Example 1 except that the adhesive composition C3 was used.

[0295] <Example 4>

[0296] To the solution of the polymer P3, 0.5 parts of a surfactant (polyoxyethylene sorbitan monolaurate, sorbitan fatty acid ester manufactured by Kao Corporation, trade name "Rheodol TW-L 120", ethylene oxide addition mole number of 20, HLB of 16.7) was further added relative to 100 parts of the polymer P3 in the solution. Except for the above aspects, an adhesive composition C4 was prepared in the same manner as the preparation of the adhesive composition C3. Except for using the adhesive composition C4, the adhesive sheet involved in this example was obtained in the same manner as the preparation of the adhesive sheet involved in Example 1.

[0297] <Example 5>

[0298] To the solution of the polymer P3, 1 part of an isocyanate crosslinking agent A1 (trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation, trade name "Coronate L", solid content concentration of 75 wt%) was added based on the solid content relative to 100 parts of the polymer P3 in the solution, and 1 part of a photoinitiator (manufactured by IGM Regins, trade name "Omnirad 369") was further added and mixed to prepare an adhesive composition C5. The adhesive sheet of this example was obtained in the same manner as the preparation of the adhesive sheet of Example 1 except that the adhesive composition C5 was used.

[0299] <Example 6>

[0300] (Preparation of Adhesive Composition)

[0301] Into a reaction container equipped with a Liebig condenser, a nitrogen inlet pipe, a thermometer and a stirring device, 75 parts of 2-ethylhexyl acrylate (2EHA) as monomer raw materials, 25 parts of acryloyl morpholine (ACMO), 3 parts of acrylic acid (AA) and 0.1 parts of 2-hydroxyethyl acrylate (HEA), and ethyl acetate as a polymerization solvent were added, and 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator were added, and solution polymerization was carried out under a nitrogen atmosphere to obtain a solution of polymer P6. The weight average molecular weight (Mw) of polymer P6 is 1.2 million. The glass transition temperature (Tg) of polymer P6 based on the composition of the above monomer raw materials is -37.4°C.

[0302] To the solution of the polymer P6, 2 parts of an isocyanate crosslinking agent A1 (trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation, trade name "Coronate L", solid content concentration of 75 wt%) and 0.7 parts of an epoxy crosslinking agent A2 (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C") were added based on the solid content, relative to 100 parts of the polymer P6 in the solution, and mixed to prepare an adhesive composition C6. The adhesive sheet of this example was obtained in the same manner as in the preparation of the adhesive sheet of Example 1, except that the adhesive composition C6 was used.

[0303] <Example 7>

[0304] To the solution of the polymer P6, 0.5 parts of a surfactant (polyoxyethylene sorbitan monolaurate, sorbitan fatty acid ester manufactured by Kao Corporation, trade name "Rheodol TW-L 120", ethylene oxide addition mole number 20, HLB 16.7) was further added. Except for the above aspects, an adhesive composition C7 was prepared in the same manner as the preparation of the adhesive composition C6. Except for using the adhesive composition C7, the adhesive sheet involved in this example was obtained in the same manner as the preparation of the adhesive sheet involved in Example 1.

[0305] <Performance Evaluation>

[0306] For each of the adhesive sheets involved in each example, the normal peeling slip SSd0 before irradiation, the water peeling slip SSw0 before irradiation, the normal peeling slip SSd1 after irradiation, and the water peeling slip SSw1 after irradiation were measured. In addition, for each of the adhesive sheets involved in each example, the normal peeling force Fd0 before irradiation, the water peeling force Fw0 before irradiation, the normal peeling force Fd1 after irradiation, and the water peeling force Fw1 after irradiation were measured. The results are shown in Table 1.

[0307] [Table 1]

[0308] Table 1

[0309]

[0310] As shown in Table 1, for the adhesive sheets of Examples 1 to 5, the stickiness can be reduced by UV irradiation. In addition, for the adhesive sheets of Examples 1 to 7, the stickiness can be reduced by water stripping. In particular, for the adhesive sheets of Examples 1 to 5 and 7, a significant reduction in stickiness was observed by at least one of water stripping and UV irradiation. In addition, for the adhesive sheets of Examples 1 to 5, a particularly significant reduction in stickiness was observed by water stripping after UV irradiation.

[0311] In addition, for the adhesive sheets of Examples 1 to 5, the peeling force can be greatly reduced by UV irradiation. In addition, for the adhesive sheets of Examples 1 to 7, the peeling force can be reduced by water peeling. In particular, for any of the adhesive sheets of Examples 1 to 5, a particularly significant reduction in peeling force was observed by water peeling after UV irradiation.

[0312] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the claims. The techniques described in the claims include various modifications and changes to the specific examples described above.

Claims

1. An adhesive sheet for wafer processing comprising an adhesive layer constituting an adhesive surface, The adhesive layer comprises an acrylic polymer as a base polymer and a surfactant, The content of the surfactant is 0.001 parts by weight or more and 5 parts by weight or less relative to 100 parts by weight of the base polymer. The viscosity of the adhesive sheet [10 -3 N / 10mm] is 30 or less, the stickiness is measured by using an evaluation sample prepared by attaching the adhesive surface of the adhesive sheet to a silicon wafer as an adherend, using at least one of the following methods A, B and C, under an environment of 23°C and 50% RH, in accordance with "10.4.1 Method 1: 180° peel adhesion relative to a test plate" of JIS Z0237:2009, at a peeling speed of 300 mm / min and a peeling angle of 180 degrees, Method A: supplying an aqueous peeling liquid to the interface between the PSA sheet and the adherend in the evaluation sample, and then measuring the stickiness when the PSA sheet is peeled from the adherend; Method B: irradiating the evaluation sample with active energy rays from the surface of the PSA sheet opposite to the adherend, and then measuring the stickiness when the PSA sheet is peeled off from the adherend; Method C: irradiating the evaluation sample with active energy rays from the surface of the adhesive sheet opposite to the adherend, supplying an aqueous peeling liquid to the interface between the adhesive sheet and the adherend, and then measuring the stickiness when the adhesive sheet is peeled from the adherend. in, The peeling force curve is represented by y=f(x). When only the reference length L is extracted from the peeling force curve along the direction of its average line, the stick-slip property [10 -3 N / 10mm] is obtained by the following general formula (1):

2. The adhesive sheet according to claim 1, wherein The peeling force measured by at least one of the following methods E, F, and G using the evaluation sample is 0.10 N / 10 mm or less, Method E: supplying an aqueous peeling liquid to the interface between the PSA sheet and the adherend in the evaluation sample, and then measuring the peeling force when the PSA sheet is peeled from the adherend; Method F: irradiating the evaluation sample with active energy rays from the surface of the PSA sheet opposite to the adherend, and then measuring the peeling force when the PSA sheet is peeled from the adherend; Method G: The evaluation sample is irradiated with active energy rays from the surface of the PSA sheet opposite to the adherend, and an aqueous peeling liquid is supplied to the interface between the PSA sheet and the adherend, and then the peeling force when the PSA sheet is peeled from the adherend is measured.

3. The adhesive sheet according to claim 1 or 2, wherein When the pressure-sensitive adhesive sheet is peeled from the adherend using the evaluation sample without irradiating the evaluation sample with active energy rays, the peel force is 0.20 N / 10 mm or more.

4. The adhesive sheet according to claim 1 or 2, wherein The adhesive layer is an active energy ray-curable adhesive layer.

5. The adhesive sheet according to claim 1 or 2, wherein The evaluation sample was used to measure the stickiness [10 -3 N / 10mm] is less than 10.

6. The adhesive sheet according to claim 1 or 2, wherein The evaluation sample was used and the stickiness [10 -3 N / 10mm] is less than 3.

7. The adhesive sheet according to claim 2, wherein The peel force measured by at least one of the method F and the method G using the evaluation sample is less than 0.050 N / 10 mm.

Citation Information

Patent Citations

  • An electric motor having a drive valve

    JP1974071517A

  • Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device

    JP2007051271A

  • Method for processing wafer

    JP2014003199A

  • Back grind tape

    JP2017212441A

  • Sheet for semiconductor-related-member processing and process for producing chip using said sheet

    CN106062928A